Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

Freeze-thaw-induced greenhouse gas emissions from a Mollisol agroecosystem: Microbial and edaphic regulation under long-term agricultural management - Dan-Dan Wang; Shan-Shan Dai; Peng He; Zhi-Ming Zhang; Jian-Ying Zhou; Ming-Hui Liu; Shi-Xiu Zhang; Lu-Jun Li (Soil and Tillage Research, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Climate-driven redistribution of Cheilinus wrasses and Acanthaster planci - Yixuan Huang; Peng Wu; Tao Zhou; Zhi Zhang; Feiyan Du; Zhizhong Xiao; Jun Li; Shihong Xu; Yongshuang Xiao (Marine Pollution Bulletin, 2026)

Estuarine gradients and climate stressors: Divergent population responses and management implications for coastal species across the Yangtze Estuary barrier - Jie Yang; Peng Wu; Tao Zhou; Zhi Zhang; Feiyan Du; Zhizhong Xiao; Jun Li; Shihong Xu; Yongshuang Xiao (Marine Environmental Research, 2026)

Asynchronous variation between aboveground carbon storage and structural complexity motivates stage-specific structural regulation across successional stages in Pinus kesiya var. langbianensis secondary forests - Zhi Liu; Hongbin Luo; Yong Wu; Shiqi Su; Yuansu Xu; Jing Li; Zhibo Yu; Lei Bao; Zongjian Peng; Hao Zhou; Xiaohan Liu; Weibin Wang; et al. (Forest Ecology and Management, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Urbanization facilitates colonization and reshapes strangler-host networks: the fate of strangler figs in a tropical urban landscape and implications for management - Yu-Xuan Mo; Huang Zou; Hai-Xia Hu; Josep Peñuelas; Zhi-Peng Wang; Bang-Xiao Zheng; Xian-Meng Shi; Su Li; Sujan Balami; Hua-Zheng Lu; Liang Song (Urban Forestry & Urban Greening, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Engineering a robust glucose oxidase: Enhanced thermostability, acid tolerance and catalytic activity drive high-level gluconic acid production - Ying-Zhi Peng; Xin-Cheng Jiang; Jing Li; Yi-Fa Yu; Jia-Yu He; Bing-Yan Xu; Xiang Lv; Qiong-Ying Wu; Shuai You; Jun Wang (Food Chemistry, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

The patterns and driving forces of orbital-to millennial-timescales East Asian summer monsoon precipitation variations during the last glaciation - Yi Li; Jingwei Zhang; Xinmiao Chen; Zhi Zhang; Qingfeng Shao; Xinggong Kong; Simin Peng (CATENA, 2026)

Red imported fire ant (Solenopsis invicta) nesting enriches soil biodiversity but simplifies nutrient cycling functional genes - Zijun Liao; Zhihong Qiao; Haocai Wang; Yiyue Zhang; Haifeng Yao; An Xie; Zhi-Peng Li; Stefan Scheu; Xin Sun (Soil Ecology Letters, 2026)

“Precursors-in-action” nanoreactor: Coordination-activated self-assembly of cu/Fe bimetallic multifunctional metalloenzyme mimics for cascade-amplified breast cancer therapy - Peng Wang; Xin-Yi Zhang; Ying-Ying Han; Zhi-Yuan Li; Qing-Hua Shen; Long-Bo Yu; Cai-Ping Tan (Chemical Engineering Journal, 2026)

Factors underlying early cross-protection elicited by a lineage 1 branch porcine reproductive and respiratory syndrome virus live vaccine candidate - Chao Li; Jinhao Li; Bangjun Gong; Jiahao Shi; Xueli Zhang; Zhenyang Guo; Lirun Xiang; Siyu Zhang; Zixuan Feng; Haonan Kang; Yan-Dong Tang; Kuan Zhao; et al. (Veterinary Microbiology, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Reverse Time Migration Imaging of Array GPR Data Based on a 2D CMWCNN Network-Driven Interpolation Strategy - Peng-Yu Li; Hong-Hua Wang; Hong-Zhao Meng; Zhi Zhang (Applied Geophysics, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Extracellular Vesicles Derived from Resveratrol-Treated BMSCs Promote the Repair of Bone Defects in Osteoporotic Rats - Yan Lv; Yongjun Du; Zhi Peng; Chengjie Ma; Zhenggang Li; Rui Xu; Jianhong Hou; Sheng Lu (Stem Cell Reviews and Reports, 2026)

Double-layered soil profile structure in an agro-pastoral ecotone revealed by geochemical characteristics: implications for wind erosion in northern North China - Jian-Yu Liu; Chun-Lei Zha; Zhi-Qiang Yin; Ling Peng; Kai-Ning Lv; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Corrigendum to ‘Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model’ [Journal of Photochemistry & Photobiology B: Biology Volume 272 (2025) 113276] - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Experimental investigation of trace helium-3 enrichment via total-reflux cryogenic distillation in a 2 K cryostat - Huan Chen; Peng Jia; Weipeng Xu; Qianxi Qu; Yiqun Chu; Dong Xu; Liguo Wang; Laifeng Li; Xiaoqin Zhi (International Journal of Refrigeration, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Decoding, Mapping, and Designing: A New Paradigm for Harnessing Umbilical Cord Mesenchymal Stem Cell Heterogeneity in Obstetric Precision Therapy - Zhang-Lu An; Zhi-Ming Wang; Wen-Hao Zhao; Li-Juan Peng; Er-Meng Gao (Stem Cell Reviews and Reports, 2026)

Soil Multi-element Fingerprinting Along Altitudinal Gradients: Insights from Changbai Mountains, China - Xuehong Li; Zhong Wu; Xiaoyan Zhu; Yinze Zhu; Peng Zhang; Yuhan Lu; Zhi Qu; Yuxiang Yuan; Tiehong Song (Chinese Geographical Science, 2026)

Tumor empowered binary macrophages regulate T cell interferon signaling to mediate immunotherapy resistance in gastric cancer - Tong Xie; Bohan Zhang; Lei Jiang; Wenwen Zhang; Boxin Liu; Yang Shi; Xiaotian Zhang; Jian Li; Yifan Zhang; Jun Zhou; Yanshuo Cao; Yakun Wang; et al. (Science Bulletin, 2026)

Intelligent key indicator decision approach based on causal mediation inference for digital wastewater treatment plants - Yu Shen; Hui-Min Li; Jian-Hui Wang; Zhi-Wei Guo; You-Peng Chen (Journal of Water Process Engineering, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Recent advances in plant-derived exosome-like nanovesicles for the treatment of liver diseases: from natural extracts to precision nanomedicine - Siyue Li; Haotian Zhang; Xinyao Zhang; Yaying Wang; Zhi Peng; Lu Yuan; Haoran Wang; Fanxing Xu; Fei Han (Chemical Engineering Journal, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Washability evaluation of coal gasification slag via an integrated sieving-water flow classification - Yufei Liu; Qian Zhang; Le Li; Haitao Wang; Peng Zhi; Baolin Zhang; Maoyu Yang; Peixiang Shi; Wei Huang (Waste Management, 2026)

A potent TGF-β heterodimer orchestrates germ cell homeostasis in fish - Ming-Tao Wang; Chun Miao; Sheng Yang; Zhi Li; Meng-Di Zhu; Jie He; Miao Ding; Si-Wei Wu; Yang Zhang; Shun Li; Meng Lu; Peng Yu; et al. (Science Bulletin, 2026)

Maximizing synergistic cobenefits of wetland conservation and restoration: A cost-effective integrated framework for urban sustainability - Xue Li; Miaomiao Sun; Xiaowen Li; Jiangtao Lv; Fangyuan Liang; Rabia Shabbir; Jiayuan Hao; Liehui Zhi; Zhiyan Xiao; Peng Li (Journal of Environmental Management, 2026)

Compounding impacts of riparian hardening and navigation erode phytoplankton community resilience in a large river ecosystem - Siyang Wang; Ditao Zhang; Peng Zhang; Yang Li; Zhi Yang (Journal of Environmental Management, 2026)

Seasonal jet stream dominates spatiotemporal heterogeneity of dry-wet status in arid Central Asia since the Holocene - Simin Peng; Yu Li; Zhansen Zhang; Zhi Zhang; Yong Ge (Global and Planetary Change, 2026)

Boron species with negative Poisson's ratio alleviating expansion-induced degradation in silicon-based anode for enhanced cycling stability - Yihao Fan; Junzhe Zhang; Lei Ma; Zhi Chen; Minglu Li; Shunan Lin; Danfeng Zhang; Peng Li; Liyong Wang; Yan-Bing He; Huiqi Wang (Chemical Engineering Journal, 2026)

Defect distribution effects in phase stability and thermal safety of HMX (1,3,5,7-tetrabitro-1,3,5,7-tetrazocane) crystals unveiled by thermal analysis integrated with small-scale slow cook-off tests - Xin Peng; Peng Zhu; Zhiyuan Jin; Chuande Zhao; Qian Yu; Fang Yang; Xiaoqi Zhi; Yu Liu; Bo Jin; Gang Li (Chemical Engineering Journal, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Rapid evaluation of the comprehensive quality of paeonol/cyclodextrin supramolecular complexes using CASSA based on near-infrared spectroscopy combined with artificial intelligence - Bo-yao Zhang; Xin-li Li; Cheng Qian; Si-min Xue; Zhi-tong Zhang; Si-yi Liu; Guo Zhang; Guo-ping Peng; Ning Ding; Yun-feng Zheng (Molecular Diversity, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Toward efficient and accurate InSAR elevation modeling via Dimensionality-Reduced MAP estimation - Wei-jian Liu; Zhuang-zhuang Wang; Zi-wei Li; Zhi-zeng Zhang; Zhong-kai Peng; Zhen-xia Yuan; Xin-bo Luan (Applied Geophysics, 2026)

Polyhydroxypregnane glycosides and deoxyoligosaccharides from Cynanchum acutum subsp. sibiricum and anticomplementary activity of its compounds - Miao-Miao Li; Xue-Ru Wang; Wen-Jing Li; Zhi-Peng Zheng; Yan Lu; Qi Wang (Natural Product Research, 2026)

Phylogeographic perspectives on conserving the endangered monotypic genus Acanthochlamys (Velloziaceae) - Dennis A. Wakhungu; Zhi-Peng Li; Amos Kipkoech; Moses C. Wambulwa; Oyetola O. Oyebanji; Richard I. Milne; Christopher Dudley; Winnie W. Mambo; Bo Xu; Jie Liu (Conservation Genetics Resources, 2026)

Front-face synchronous fluorescence spectroscopy coupled with PLSR for rapid quantitative analysis of Chinese five-spice powder composition - Fei-Yue Chen; Li-Fen Zhang; Hong-Yan Pan; Xia Huang; Pei Yi; Zhi Jin; Peng-Hui Zhu; Jin Tan (Food Research International, 2026)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury after SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2026)

Semi-analytic Solutions for Long-Term Stress–Strain Behavior of Rock Salt Using Fractional Burgers Model and Transformed Differential Quadrature Method - Yong Zhi Zhao; Junliang Li; Ming Peng; Yan Zhu; Zhenming Shi (Rock Mechanics and Rock Engineering, 2026)

Soil aggregate-mediated dynamics of microbial necromass under contrasting cropland management practices - Wen-Jun He; Jie-Yu Gao; Xin-Xin Jing; Peng Chen; Lu-Ping Ye; Zhi-Guo Li; Yi Liu; Chen-Hao Lyu (Plant and Soil, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

In vitro screening and in vivo evaluation of anti-virulence herbal compounds against Streptococcus agalactiae in tilapia (Oreochromis niloticus) - Ming-Li Xiang; Zi-Chen Zhao; Gui-Hua Li; Wei Tang; En-Peng Chen; Shui-Feng Qin; Yan Wang; Heng-Wei Deng; Zhi-Hong Zhong; Yun Sun; Wei-Liang Guo; Yong-Can Zhou (Aquaculture, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Evaluating the environmental impact of hydrothermal cracking solid organic fertilizer: Carbon and nitrogen retention and toxic metals analysis - Rui Xia; Xiao-xiao Yang; Jue Wang; Kai-le Li; Zhi-peng Sun; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Journal of Environmental Sciences, 2026)

A prior knowledge-enhanced Transformer model for data anomaly identification and processing in industrial park wastewater treatment plants - Wen-Chao Li; Hui-Min Li; Zhi-Wei Guo; Peng Yan; Yu Shen; You-Peng Chen (Water Research, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Impact of algal blooms on phosphorus migration: Insights from laboratory and field cultivation enrichment experiments in the yangtze river estuary - Yu-Yuan Wang; Zhi-Li Guo; Han-Lin Jiang; Yuan-Zhe Ni; Li-Min Zhou; Gui-Peng Yang; Xiao-Yan Cao (Estuarine, Coastal and Shelf Science, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Mussel Production in the Global Blue Food System: Current Status, Sustainability Challenges, and Future Trajectories - Fan Li; Hai-Jie Gao; Yun-Lin Ni; Peng-Zhi Qi (Fishes, 2026)
This review examines the status, challenges, and future trajectories of global mussel aquaculture within the blue food system. Despite steady production growth, mussels’ relative contribution to total bivalve output has significantly declined over recent decades due to disproportionate expansion of oyster, clam, and scallop sectors. A major geographical production shift has occurred, with Asia, spearheaded by China, emerging as the dominant region, supplanting traditional European producers while the Americas rapidly ascend. China’s overwhelming dominance in overall bivalve production starkly contrasts with its underdeveloped mussel sector, where growth lags behind other bivalves despite substantial absolute increases, reflecting a fundamental restructuring of species composition. The industry faces interconnected sustainability constraints: persistent vulnerabilities in spat supply stemming from environmental variability, hatchery limitations, and disease transmission risks; escalating environmental stressors including climate change impacts, harmful algal blooms, pollution, and pathogens; structural flaws in value chains characterized by fragmented production, market volatility, and underutilized byproducts; and governance challenges related to spatial access and licensing inefficiencies. This review advocates for a comprehensive strategy to boost the mussel aquaculture. These encompass advancing hatchery technology and genetic breeding programs, implementing ecosystem-based management such as multi-trophic systems and AI-enhanced environmental monitoring, restructuring value chains through producer cooperation and high value product diversification, and establishing science-based spatial planning frameworks with streamlined governance. Addressing these challenges holistically is critical to position mussel farming as a resilient pillar of sustainable blue food production capable of reconciling ecological integrity with economic viability and social equity.

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Combined with wavelet time frequency analysis and lightweight deep convolutional networkintelligent recognition of coal rock acoustic emission signal - Zhong-kai Peng; Wei-jian Liu; Zhi-zeng Zhang; Zhen-xia Yuan; Shi-lei Zhen; Zhuang-zhuang Wang; Xin-bo Luan; Jian-bo Li; Hao-yang Li; Bi-qi Yuan; Shuai Teng; Zi-wei Li (Applied Geophysics, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

Advances in understanding the neurotoxicity of lead, cadmium, arsenic, and therapeutic strategies - Yi-Ling Li; Zhi-Xin Huang; Jian-chao Peng; Thanh-Tung Ho; Hai Huang; Michael Aschner; Yue-Ming Jiang (Toxicology Letters, 2026)

A new Coniopteris (Dicksoniaceae) from the Middle Jurassic of the Baojishan Basin, Gansu, China, with discussion on its heteromorphic pinnule characteristics - Lan-Xing Wei; Cun-Lin Xin; Zhi -Peng Jiao; Fang-Fang Zhang; Hong Li (Review of Palaeobotany and Palynology, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Quantitative assessment of residual carbon content and oxidative shrinkage behavior of coal gasification slag through in situ high-temperature stage microscope - Bin Xue; Qian Zhang; Le Li; Baolin Zhang; Xiangyang Li; Peng Zhi; Yujing Yang; Wei Huang (Fuel, 2026)

Sulfone site enables H2O2 practical fabrication over metal-free photocatalyst - Zhi-Peng Tao; Lin Liu; Ke-Chao Wang; Chen-Ning Li; Jia-Qi Chu; Zhen-Hui Kang; Zheng-Bo Han (Chemical Engineering Journal, 2026)

Retraction notice to “A chitosan-camouflaged nanomedicine triggered by hierarchically stimuli to release drug for multimodal imaging-guided chemotherapy of breast cancer” [Carbohydrate Polymers 335 (2024) 122073] - Pei Wang; Zhi Peng; Yanyan Zhang; Xuejing Zhang; Xia Chen; Fan Li; Bo Chen; Shiwei Niu; Kaili Du; Li-Min Zhu (Carbohydrate Polymers, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

amh alleles on XY sex chromosomes regulate male differentiation in amphidiploid Carassius auratus - Chun Miao; Meng Lu; Miao Ding; Ming-Tao Wang; Zhi Li; Tian-Zi Yao; Zhi-Xuan Zhu; Wen-Xuan Du; Jun-Sheng Niu; Xiao-Juan Zhang; Shun Li; Peng Yu; et al. (Science China Life Sciences, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Cineole alters liver fat metabolism and enriches the fatty acid content of eggs in laying hens - Kun-kun Zhang; Zhi-hui Jiang; Zi-yan Li; Yue-teng Xing; Kun-peng Zhang (Natural Product Research, 2025)

The Effects of Lead, Cadmium and Arsenic Exposure Alone or in Combination on Neurotoxicity Through Neural Signaling Pathways - Zhi-Xin Huang; Yi-Ling Li; Jian-Chao Peng; Thanh-Tung Ho; Hai Huang; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Novel real-time quantitative RT-PCR for detection of PRRSV-1 and PRRSV-2 strains circulating in China: A study based on whole-genome characteristics and epidemiological features - Bangjun Gong; Lirun Xiang; Jinhao Li; Chao Li; Jiahao Shi; Zhenyang Guo; Siyu Zhang; Zixuan Feng; Haonan Kang; Xueli Zhang; Ziyu Song; Chaoliang Leng; et al. (The Veterinary Journal, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Micron-sized iron-sulfur minerals orchestrate micro-interface redox processes for sustainable wastewater treatment - Xin-Han Chen; Ze-Fan Chen; Chen-Peng Fang; Zhi-Zeng Zhao; Xiao-Qiang Cao; Jian Zhang; Zhao-Jing Zhu; Gang Zhou; Yi-Fan Wang; Lu-Cheng Fan; Li-Jiang Wu (Journal of Water Process Engineering, 2025)

A novel approach for expeditiously assessing residual carbon recovery from coal gasification slag - Baolin Zhang; Qian Zhang; Le Li; Yufei Liu; Chenming Gao; Bin Xue; Peng Zhi; Wei Huang (Fuel, 2025)

Novel hierarchical interpenetrating lattice metamaterials with superior energy absorption - Xuhui Zhang; Miao Zhao; Xinwei Li; Chen Tian; Feiyue Su; Bei Peng; Zhi Zeng (Engineering Structures, 2025)

Ethylene oxide side chains and rhodanine end-groups incorporated in a star-shaped cathode interface molecule for high-performance organic solar cells - Zhi-Yong Qiu; Meng-Ting Wang; Peng Liu; Yu-Long Peng; Zaifang Li; Fang Yang; Lijian Zuo; Shi-Yong Liu (Chemical Engineering Journal, 2025)

Confinement-accelerated local *CO spillover at semi-enclosed tandem heterointerface for efficient CO2-to-C2 conversion - Zhi-Yuan Wang; Guoqiang Lu; Mulin Yu; Yu-Feng Tang; Peng-Fei Sui; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Chemical constituents from Clinopodium chinense and their chemotaxonomic significance - Li Yan; Wan-Bai Su; Zhi-Yang Tang; Yang Yu; Jin-Song Liu; Yun-Peng Sun; Guo-Kai Wang (Biochemical Systematics and Ecology, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Simulation on the propagation characteristics of TEM pseudo-wavefield - Jun-jie Xue; Ke-rui Fan; Xin Wu; Zhi-peng Qi; Wen-han Li; Jiang-wei Cui (Applied Geophysics, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Adaptive sliding mode control for underactuated ship-mounted cranes with dead zones and actuated/unactuated state constraints - Xin Zhang; Zengcheng Zhou; Yihao Shi; Ming Li; Wei Peng; Chen Song; Zhi Li; Xingong Cheng; Menghua Zhang (Ocean Engineering, 2025)

Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Genesis of the Pulang polymetallic mineralization system in Yunnan Province, China: Insights from in situ trace element and S isotope analyses of pyrite - Xiao-Yu Zhao; Zi-Chao Tang; Ming-Guo Deng; Wen-Chang Li; Jing-Wei Xu; Yan Su; Zhi-Peng Li; Lei Wang (Journal of Geochemical Exploration, 2025)

Integrative machine learning and molecular insights into ZEN degradation by Apiotrichum mycotoxinivorans - Zhi-Kai Yang; Yun Huang; Xue-Ling Huang; Dan Huang; Liang Peng; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Chemical Engineering Journal, 2025)

Litter complexity rather than land-use intensity emerges as a key driver of taxonomic and isotopic diversity of Collembola in urban systems - Saichao Zhang; Zhi-Peng Li; Bin Wang; Haifeng Yao; Zhihong Qiao; Anton Potapov; Stefan Scheu; Xin Sun (Biology and Fertility of Soils, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Impacts of dams on fish habitat connectivity greatly outweigh climate change in the Jinsha river basin, China - Xiongfeng Bai; Peng Zhang; Zhi Yang; Ditao Zhang; Xianghong Dong; Siyang Wang; Sun Heying; Yunye Feng; Shuang Li; Lihua Xiong; Jianbo Chang (Journal of Hydrology, 2025)

Zoonotic pathogen-driven antibiotic resistance emerges in urban soils: A large-scale study in 13 cities across China - An Xie; Wenjuan Xu; Zhi-Peng Li; Bin Wang; Alexei V. Tiunov; Patrick O'Connor; Jian-qiang Su; Qiansheng Huang; Faith Ka Shun Chan; Matthias C. Rillig; Xin Sun (Journal of Hazardous Materials, 2025)

Synergistic quorum quenching to the diffusible signal factor and AHLs mediated quorum sensing in Thiothrix controlling filamentous sludge bulking - Rui Liu; Lin Feng; Jie Li; Zhuo-Li Yan; Jian-Hong He; Yue Zhi; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Environmental Chemical Engineering, 2025)

Effects of fertilization and different straw return methods on soil fertility and rice yield in double-season paddy fields - Nan Zhang; Jiong Wen; Lingyu Bai; Xiaxin Wei; Tao Li; Yuefeng Tang; Shiming Su; Zhi Peng; Xibai Zeng (Journal of Environmental Chemical Engineering, 2025)

Dynamically cross-linked polyethylene vitrimers: An alternative approach to high-performance high-voltage cable insulation - Zhuolin Zhang; Kangning Wu; Haoran Sui; Ge Zhao; Youshen Wu; Chenhui Cui; Peng Zhao; Kai Yang; Lisheng Zhong; Baoquan Wan; Shengtao Li; Zhi-Min Dang; et al. (Chemical Engineering Journal, 2025)

Divergent effects of cropland management practices and global change factors on microbial necromass across ecosystems: implications for soil organic carbon - Chen-Hao Lyu; Wen-Jun He; Peng Chen; Xin-Xin Jing; Guo-Shi Zhang; Run-Qin Zhang; Zi-Yan Li; Zhi-Guo Li; Yi Liu (CATENA, 2025)

Undescribed isoprenoids obtained from Dictamnus dasycarpus Turcz and their cytotoxic activities - Sun Ye; Si-Yi Wang; Yang Xu; Jia-Tong Wu; Juan Pan; Zhi-Chao Hao; Wei Guan; Zhen-Peng Xu; Yuan-Yuan Zhou; Shao-Wa Lv; Qing-Shan Chen; Li-Li Zhang; et al. (Natural Product Research, 2025)

Unravelling the mechanisms underlying marine redox shifts during sedimentary manganese metallogenesis: insights from the Carboniferous Muhu deposit, China - Zhi-Guo Dong; Bang-Lu Zhang; Lian-Chang Zhang; Fei-Yu Dong; Jie Li; Zi-Dong Peng; Bo Wan; Chang-Le Wang (Mineralium Deposita, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Agroforestry soil organic carbon: microbial top regulation, mineral subsoil dominance - Dongxi LIAO; Shuotong CHEN; Jiarun XU; Zixu ZHANG; Zhencui JIANG; Yaobin LI; Jianniu ZHANG; Wei ZHAO; Xiaocui MA; Wenhai MI; Peng GAO; Zhi DONG; et al. (Pedosphere, 2025)

Genomic analysis of Vibrio fluvialis QY27 related to its deep-sea environment adaptation - Qun-Jian Yin; Meng-Yu Liu; Li-Chang Tang; Peng-Fei Zheng; Xin Liu; Hong-Zhi Tang (Marine Genomics, 2025)

Revisiting the quantitative relationship between groundwater evapotranspiration and water table depth: A numerical study - Shu-Cong Tan; Xiao-Wei Jiang; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Li Wan; Yi-Jian Zeng (Journal of Hydrology, 2025)

From leachate to dipteran insects in municipal solid waste landfills: The sink and transfer of PFASs driven by environmental conditions - Huazu Liu; Xinxin Peng; Wanqi Shi; Wei Yang; Zhexin Li; Chuanqiao Zhou; Shenhua Qian; Xiaoming Wang; Yue Zhi; Megumu Fujibayashi; Kuba Takahiro; Wei Li (Journal of Hazardous Materials, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Long-term cadmium stress influenced the immune response of Pardosa pseudoannulata by modulating its gut microbiota and hemolymph metabolome - Jinjin Li; Yuan-de Peng; Rong Zhou; Jie Peng; Qingling She; Xinyi Yang; Juan Wang; Zhi Wang; Qisheng Song (Journal of Environmental Sciences, 2025)

Chalcogen heteroatom engineering of non-halogenated volatile solid additives based on phthalic anhydride enables high-performance polymer solar cells - Tao Li; Yu Zhu; Xiujie Peng; Heng Li; Linglong Ye; Qingyuan Wang; Zhi-Guo Zhang; Ping Shen; Chao Weng (Chemical Engineering Journal, 2025)

Correction to: Overexpression of Tau Rescues Nogo-66-Induced Neurite Outgrowth Inhibition In Vitro - Yu-Chao Zuo; Hong-Lian Li; Nan-Xiang Xiong; Jian-Ying Shen; Yi-Zhi Huang; Peng Fu; Hong-Yang Zhao (Neuroscience Bulletin, 2025)

miR-2400 promotes proliferation of bovine skeletal muscle-derived satellite cells by regulating MAGED1 genes expression - Li Yang; Hai-Jing Luo; Zhi-An Gong; Wen-Tian Zhang; Jing-Xuan Cui; Xue-Peng Fu; Wei-Wei Zhang (Journal of Muscle Research and Cell Motility, 2025)

Structurally diverse oxygen-containing aromatic compounds with anti-inflammatory activity from Aspergillus sp. LY-1-2 - Chu-Qiao Wang; Jinzhi Pan; Shuang-Zhi Yuan; Chao Yuan; Fei-Xiang Ji; Dan Feng; Xiao-Ping Peng; Qian Luo; Hong-Xiang Lou; Gang Li (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Assessing the nicotinic acetylcholine receptor-mediated enantioselective neurotoxicity of a neonicotinoid-like pollutant, chiral sulfoxaflor: Insight from the two asymmetric centers - Zhi-Cong He; Tao Zhang; Xin-Fang Lu; Rui Li; Wei Peng; Qiong Mei; Qi-Zhao Wang; Fei Ding (Journal of Hazardous Materials, 2025)

Circular utilization of oilfield wastewater for sustainable flotation separation of coal gasification slag: Advancing waste-to-resource strategies for cleaner production - Guixia Fan; Yali Shang; Zhi Cao; Mengjie Li; Guosheng Li; Kai Jia; Fanfan Zhang; Yijun Cao; Jianbo Zhang; Daoguang Teng; Peng Li (Journal of Cleaner Production, 2025)

Laminaria Japonica hydrolysate as a novel biostimulant for enhancing DHA accumulation in Aurantiochytrium limacinum - Jia-Xue Lin; Ying Wang; Shao-Geng Zhao; Bei-Chen Huang; Yue Zhang; Zhi-Qiang Wang; Sheng-Jie Li; Qian Liu; Yan Ma; Jing-Run Ye; Hai-Ying Wang; Zhi-Peng Wang (World Journal of Microbiology and Biotechnology, 2025)

Nuclear magnetic resonance-based metabolomic study of rat brain after different intensity treadmill running - Ni Zeng; Jie-Ting Li; Zhi-Juan Zhang; Zhi-Peng Yan; Tao Liao; Guo-Xin Ni (Journal of Physiology and Biochemistry, 2025)
Previous studies have revealed that different intensities of exercise training have an impact on cognition. However, the cognitive effects of different intensities of exercise and its underlying mechanisms are not fully understood. The aim of this paper was to investigate the effects of different intensities of treadmill exercise on cognition in rats from the perspective of metabolomic analysis. In this study, ninety-six male rats were randomly divided into four groups: control group (CON group, n = 24), low-intensity running group (LIR group, n = 24), medium-intensity running group (MIR group, n = 24), and high-intensity running group (HIR group, n = 24). After 4 weeks of treadmill running, rats in the LIR group located the platform significantly faster than those in the CON( p = 0.027) and HIR( p = 0.011) groups. After 8 weeks of treadmill running, rats in the LIR and MIR groups also found the platform more quickly than those in CON group ( p = 0.003 and p = 0.015, respectively). Additionally, rats in the MIR group showed significantly increased superoxide dismutase (SOD)/catalase (CAT) in the hippocampus compared with those exposed to HIR( p = 0.03), LIR( p = 0.0008), and CON( p = 0.0004). Metabolomic analysis revealed that, after 8 weeks of running, 14 metabolites with similar characteristics differed between the MIR and HIR groups compared to the CON group. The LIR group showed significant alterations in 12 key metabolites compared to the CON group. The LIR, MIR, and HIR groups also demonstrated significant changes in 3, 4, and 3 metabolic pathways respectively, when compared to the CON group. In conclusion, the above results indicate that LIR can effectively decrease fumarate accumulation, thereby enhancing the TCA cycle and brain energy metabolism which in turn improved cognitive function, while MIR can modify glutathione metabolism to alleviate oxidative stress (OS), supporting cognitive function.

Two new megastigmane glycosides from the leaves of Nicotiana tabacum and their anti-inflammatory activities - Peng-fei Yang; Wei Wu; Hang-hang Han; Qing-fu Wang; Lei Li; Ze-ning Wang; Duo-bin Mao; Zhi-fei Chen (Natural Product Research, 2025)

Mechanical Properties of Granular Sea Ice Under Uniaxial Compression: A Comparison of Piled and Level Ice - Yubo Liu; Qingkai Wang; Peng Lu; Zhijun Li; Zhixing Li; Zhi Zong; Limin Zhang (Journal of Marine Science and Engineering, 2025)
The proportion of granular ice in sea ice layers has markedly increased due to global warming. To investigate the uniaxial compressive behavior of granular sea ice, we conducted a series of experiments using natural piled and level ice samples collected from the Bohai Sea. A total of 311 specimens were tested under controlled temperature conditions ranging from −15 °C to −2 °C and strain rates varying from 10−5 to 10−2 s−1. The effects of porosity, strain rate, and failure modes were studied. The results show that both the uniaxial compressive strength and uniaxial compressive elastic modulus were dependent on strain rate and porosity. Granular sea ice exhibited a non-monotonic strength dependence on strain rate, with the strength increasing in the ductile regime and decreasing in the brittle regime. In contrast, the elastic modulus increased monotonically with the strain rate. Both the strength and elastic modulus decreased with increasing porosity. Level ice consistently demonstrated higher strength and an elastic modulus than piled ice at equivalent porosities. Unified parametric models were developed to describe both properties across a wide range of strain rates encompassing the ductile-to-brittle (DBT) regime. The experimental results show that, as porosity decreased, the transition strain rate of granular sea ice shifted from 2.34 × 10−3 s−1 at high porosity (45%) to 1.42 × 10−4 s−1 at low porosity (10%) for level ice and 1.87 × 10−3 s−1 to 1.19 × 10−3 s−1 for piled ice. These results were compared with classical columnar ice models. These findings are useful for informing the design of vessel and coastal structures intended for use in ice-covered waters.

Spatio-temporal graph neural network fused with maritime knowledge for predicting traffic flows in ports - Qiang Mei; Zhaoxuan Li; Qinyou Hu; Xiaoying Zhi; Peng Wang; Yang Yang; Xiliang Liu (Regional Studies in Marine Science, 2025)

A hydrogel-based composite facilitates efficient and recyclable tetracycline biodegradation in aquatic environments - Ze-Hua Cui; Qian He; Zhi-Peng Li; Yao Deng; Xiao-Ping Liao; Chaoqun Zhang; Jian Sun; Hao Ren; Lu Han (Environmental Research, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

The defected cobalt sulfide for efficient solar water evaporation: Understanding cobalt-based material induced photothermal conversion - Qing Wan; Peng Xiang; Congming Tang; Xinli Li; Zhi Chen (Chemical Engineering Journal, 2025)

Biosynthesis of D-threitol from biomass-derived xylose by engineering Trichosporonoides oedocephalis - Jingyi Xu; Yue Tang; Yuqi Peng; Zhi Chen; Xin Ju; Liangzhi Li (World Journal of Microbiology and Biotechnology, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Differential magmatism and tectonic evolution during the rift stage within the Baiyun Sag of the Pearl River Mouth Basin in the northern South China Sea - Bo Yan; Xuan-Long Shan; Zhe Wei; Guo-Li Hao; Peng-Lin Zhang; Ling Ma; Zhi-Hao Wang; Pu-Jun Wang; N.G. Boriskina (Gondwana Research, 2025)

Rapid absolute quantification of glucose and fructose isomers in honey using a boronic acid-based reactive matrix by MALDI-TOF/TOF tandem mass spectrometry - Zhang-Na Qin; Jia-Min Chen; Jia-Wei Li; Zhen-Peng Zhen; Qi-Zhao Chen; Zhi-Qiang Zhang; Gui-Hua Wang; Yu-Feng Gao (Food Chemistry, 2025)

An analytical solution to the radiation-convective heat transfer in a parallel-plates direct absorption solar heat collection duct - Chao-Hua Peng; Chuan-Shuai Dong; Li-Zhi Zhang (Energy and Buildings, 2025)

Quick and reliable approach for rating underground engineering rock mass based on RMR system - Peng He; Zhi-kang Li; Feng Jiang; Gang Wang; Wen-peng Yuan; Zheng-hu Ma; Chuan-xin Yang; Zihao Jiang (Applied Geophysics, 2025)

The heterogeneity of travel mode choice behavior under unplanned metro service disruptions - Qing-Chang Lu; Xin-Yu Zuo; Chao Chen; Zhi Dong; Peng-Cheng Xu; Jing Li (Transportation Research Part D: Transport and Environment, 2025)

An adjustable robust optimization model under dynamic informer-based framework for industrial renewable energy systems - Aoqun Ma; Feifei Shen; Zhi Li; Xin Peng; Weimin Zhong (Process Safety and Environmental Protection, 2025)

Quantifying thresholds of key drivers for ecosystem health in large-scale river basins: A case study of the upper and middle Yellow River - Xue Li; Kunxia Yu; Guoce Xu; Peng Li; Zhanbin Li; Peng Shi; Lu Jia; Zhi Yang; Zihui Yue (Journal of Environmental Management, 2025)

Rational design of phospholipase D to enhance thermostability and catalytic activity for efficient biocatalytic phosphatidylserine synthesis - Peng Zhang; Xin-An Mao; Xiao-Li Kong; Jin-Song Gong; Zi-Kai Wang; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Chemistry, 2025)

Anterior Cingulate Cortex Contributes to the Hyperlocomotion under Nitrogen Narcosis - Bin Peng; Xiao-Bo Wu; Zhi-Jun Zhang; De-li Cao; Lin-Xia Zhao; Hao Wu; Yong-Jing Gao (Neuroscience Bulletin, 2025)

Extreme precipitation analysis in Central Asia based on the two-step kappa approach under global change - Kaiya Sun; Peng Yang; Jun Xia; Heqing Huang; Yaning Chen; Zhi Li; Yanchao Zhu; Jingxia Song; Xiaorui Shi; Xixi Lu (Climate Dynamics, 2025)

Failure Characteristics and Control Strategies of Overlying Remaining Coal Pillars in Close-Distance Coal Seam Mining - Wei-guang Ren; Hui Yuan; Zhi-gang Deng; Yun-peng Li; Wen-xin Li (Applied Geophysics, 2025)

Effect of Sodium Para-Aminosalicylic Acid on Cuproptosis in PC12 Cells Exposed Manganese, Iron, and Copper - Hai Huang; Thanh-Tung Ho; Zhi-Xin Huang; Yi-Ling Li; Jian-Chao Peng; Viet-Phuong-Nguyen Nguyen; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Tumor cell-derived N-acetyl-aspartyl-glutamate reshapes the tumor microenvironment to facilitate breast cancer metastasis - Jie Xia; Lixing Zhang; Wucheng Zhu; Juchuanli Tu; Xilei Peng; Qiaodan Deng; Siqin Li; Xueyan He; Haonan Dong; Cuicui Liu; Xian Chen; Jiahui Xu; et al. (Science Bulletin, 2025)

Preconception maternal hyperoxia exposure causes cardiac insufficiency through induction of mitochondrial toxicity in mice offspring - Dan Chen; Zhi-xuan Xing; Sheng-peng Li; Tao Lu; Jia-xin Wang; Ya-xian Wu; Qing-feng Pang (Reproductive Toxicology, 2025)

Novel streamflow forecast method of WRF/WRF-Hydro one-way coupling assisted by the GNSS and FY-4A satellite in areas with scarce data - Qingzhi Zhao; Pengfei Geng; Hongwu Guo; Zufeng Li; Yuzhu Du; Yanbing Yue; Yibin Yao; Wenjie Peng; Yatong Li; Wei Wang; Xiaoya Zhang; Zhi Ma (Journal of Hydrology, 2025)

Effects of organic material addition on carbon cycling and soil fertility in paddy soil - Nan Zhang; Lingyu Bai; Xiaxing Wei; Tao Li; Yuefeng Tang; Jiong Wen; Zhi Peng; Yang Zhang; Yanan Wang; Xibai Zeng; Shiming Su (Journal of Environmental Management, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)

Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)
Subarachnoid hemorrhage (SAH) is a type of stroke with a high disability and mortality rate. Apoptosis caused by massive damage to mitochondria in neuron cells and inflammatory responses caused by high extracellular ATP lead to poor outcomes. USP30 is a deubiquitinating enzyme that inhibits mitophagy, resulting in a failure to remove damaged mitochondria in a timely manner after SAH; nevertheless, the pathway through which USP30 inhibits mitophagy is unknown. This study evaluated the neuroprotective role and possible molecular basis by which inhibiting USP30 to attenuate SAH-induced EBI by promoting neuronal mitophagy. We used an in vitro model of hemoglobin exposure and an in vivo model of intravascular perforation. Increased expression of USP30 was found after SAH in vivo and in vitro, and USP30 inhibition expression in SAH mice treated with MF094 resulted in significant improvement of neurological injury and inflammatory response and mediated good outcomes, suggesting a neuroprotective effect of USP30 inhibition. In cultured neurons, inhibition of USP30 promoted ubiquitination modification of mitochondrial fusion protein 2 (MFN2) by E3 ubiquitin ligase (Parkin), separating damaged mitochondria from the healthy mitochondrial network and prompting mitophagy, causing early clearance of damaged intracellular mitochondria, and reducing the onset of apoptosis. The high extracellular ATP environment was meliorated, reversing the conversion of microglia to a pro-inflammatory phenotype and reducing inflammatory injury. USP30 inhibition had no autophagy-promoting effect on structurally and functionally sound mitochondria and did not inhibit normal intracellular ATP production. The findings suggest that USP30 inhibition has a neuroprotective effect after SAH by promoting early mitophagy after SAH to clear damaged mitochondria.

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

An extensin-like gene OsPEX1 plays key roles in temperature stress response in rice - Jieni Li; Ao Li; Yue Wang; Zhi-Hao Wu; Xiaohong Li; Jie Meng; Chen Liang; Yuxin Song; Na Liu; Wanzhen Gao; Haifeng Peng; Yingxue Yang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Reconstruction of well-logging data using unsupervised machine learning-based outlier detection techniques (UML-ODTs) under adverse drilling conditions - Jing-Rui Chen; Rui-Zhao Yang; Ting-Ting Li; Yun-Di Xu; Zhi-Peng Sun (Applied Geophysics, 2025)

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Functional characterization of an epsilon glutathione S-transferase (SfGSTe9) associated with insecticide detoxification in Spodoptera frugiperda - Wei-Huan Xu; Meng-Yao Zhu; Zhi-Heng Xu; Xiao-Jie Li; Chao-Yang Peng; Xiao-Pei Fan; Yong-Qiang Li (Pesticide Biochemistry and Physiology, 2025)

A systematic model- and experimental approach to hydro-mechanical and thermo-mechanical fracture processes in crystalline rocks - Olaf Kolditz; Christopher McDermott; Jeoung Seok Yoon; Mostafa Mollaali; Wenqing Wang; Mengsu Hu; Tsubasa Sasaki; Jonny Rutqvist; Jens Birkholzer; Jung-Wook Park; Chan-Hee Park; Hejuan Liu; et al. (Geomechanics for Energy and the Environment, 2025)

Protection of glutamine: The NF-κB/MLCK/MLC2 signaling pathway mediated by tight junction affects oxidative stress, inflammation and apoptosis in snakehead (Channa argus) - Xue-qin Wu; Ji-wu Wan; Zhi-nan Yang; Hong-jian Liu; Yue Chang; Si-bo Peng; Xiao-tian Niu; Yi-di Kong; Min Li; Xiu-mei Chen; Gui-qin Wang (Fish & Shellfish Immunology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Assessment of eco-driving strategies on carbon emissions for hybrid vehicles through portable emissions measurement systems - Bo-wen Li; Zhi-heng Chen; Xing-hang Zhu; Zhe Zhang; Zhong-ren Peng; Hong-mei Zhao; Hong-di He (Atmospheric Pollution Research, 2025)

5-Azacytidine inhibits endoplasmic reticulum stress and apoptosis of nucleus pulposus cells by preserving PPARγ via promoter demethylation - Peng Cheng; Huan Li; Hai-Wei Chen; Zhi-Qiang Wang; Pei-wu Li; Hai-Hong Zhang (In Vitro Cellular & Developmental Biology - Animal, 2025)

The influence of greening management and landscape patterns on plant diversity in urban green spaces in Danzhou, China - Mei-Hui Zhu; Qian Li; Jia-Li Yuan; Josep Padullés Cubino; Joel B. Johnson; Jian-Peng Cui; Mir Muhammad Nizamani; Zhi-Xin Zhu; Hua-Feng Wang (Urban Forestry & Urban Greening, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

Impact of different continuous fertilizations on the antibiotic resistome associated with a subtropical triple-cropping system over one decade - Jin Zheng; Ya-Ying Li; Yu-Sheng Lu; Dan Wang; Chong Liu; Huan-Long Peng; Chao-Hong Shi; Kai-Zhi Xie; Kun Zhang; Li-Li Sun; Chang-Min Zhou; Wen-Jie Gu (Environmental Pollution, 2025)

Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Loaded Mir-29-3p Targets AhR to Improve Juvenile Idiopathic Arthritis via Inhibiting the Expression of IL-22 in CD4+ T Cell - Xinyi Wei; Kunpeng Sui; Yuanyuan Peng; Sha Li; Yu Fang; Zhi Chen; Xiao Du; Xue Xie; Haiming Tang; QiuYue Wen; JingWei Li; Meilin He; et al. (Stem Cell Reviews and Reports, 2025)

Current progress in the development of biosensors based on nanomaterials for the detection of inorganic arsenic - Y.P. Zheng; W. Li; T.H. Liu; X. Li; Y.F. Tang; D. Zhi; B. Peng; Y.Y. Zhou (International Journal of Environmental Science and Technology, 2025)

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

The research of nicotinamide and β-arbutin on reducing melanin content in the skin of leopard coral grouper (Plectropomus leopardus) - Zhi Bin Sun; Shi Ying Liu; Xin An Wang; Ai Jun Ma; Zhi Hui Huang; Zhi Feng Liu; Wei Heng Sun; Peng Fei Yan; Dong Hui Gou; Hui Yu Xiao; Hao Zhe Li; Vorathep Muthuwan; et al. (Aquaculture, 2025)

Reproductive toxicity of bisphenol A and nitro-bisphenol A in male zebrafish at environmentally relevant concentrations - Chao Wang; Shuyi Zhang; Zijin Shao; Peijie Sun; Jiran Zhang; Shaoping Zhang; Jian Kong; Hong Zhi; Li Li; Mingshu Li; Jie Yu; Zhenming Liu; et al. (Science of The Total Environment, 2025)

Foliar uptake, translocation and its contribution to Cadmium accumulation in rice - Zhen Zhu; Jianwei Peng; Pengyue Yu; Jiangchi Fei; Zhi Huang; Yaocheng Deng; Xiaoe Yang; Jipeng Luo; Tingqiang Li; Ying Huang (Science of The Total Environment, 2025)

Monitoring China's solar power plant in-use stocks and material recycling potentials using multi-source geographical data - Shujun Li; Peng Wang; Qian Zhang; Jiashuo Li; Zhi Cao; Wen Li; Wei-qiang Chen (Resources, Conservation and Recycling, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Development of a platform strain for integration expression of phospholipase D and its application in improving phosphatidylserine content of egg yolk - Peng Zhang; Xiao-Li Kong; Jin-Song Gong; Zhi-Yuan Yao; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2025)

Hybrid multi-stage steel footprinting unveils a more interdependent material foundation of the global economy - Xinyi Li; Chao Zhang; Xue Yang; Ziqian Xia; Zhi Cao; Peng Wang; Heming Wang; Tao Wang; Gang Liu; Wei-Qiang Chen (Ecological Economics, 2025)

Rapid gelation of mechanical robust, conductive, and self-healing lignocellulosic nanofibrils hydrogel toward flexible sensor over a broad temperature spectrum - Zhi-Chao Xu; Yu-Qin Yang; Xiao-Wen Pang; Baiyu Jiang; Peng-Fei Mao; Li-Xiu Gong; Binghao Wang; Li Peng; Long-Cheng Tang; Shi-Neng Li (Chemical Engineering Journal, 2025)

Fostering rehydration and facilitating bioactive release through cellulose-assisted leaf surface treatment - Shangxu Jiang; Peng Li; Li Li; Nasim Amiralian; Divya Rajah; Zhi Ping Xu (Carbohydrate Polymers, 2025)

Development of a Novel TBM Tunnelling Test Platform and Its Application in Rock–Machine Interaction Analysis - Wei-Qiang Xie; Xiao-Li Liu; Rui-Peng Qian; Jian Chen; En-Zhi Wang; Wei Hong (Rock Mechanics and Rock Engineering, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Roadside measurement of N2O and CH4 emissions from vehicles in Hong Kong - Mengyuan Chu; Peter Brimblecombe; Nirmal Kumar Gali; Meisam Ahmadi Ghadikolaei; Peng Wei; Xin Li; Shiyi Yang; Yuanhui Wei; Zhi Ning (Science of The Total Environment, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Anti-photoaging activity of triterpenoids isolated from Centella asiatica - Yi-yun Dang; Tao Liu; Yu-die Liu; Jia-yi Li; Yi Jing; Miao-jie Yang; Han Zhang; Miao-miao Jiang; Hong-hua Wu; Wen-zhi Yang; Nan Li; Peng Zhang (Phytochemistry, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Machine learning-assisted laccase-like activity nanozyme for intelligently onsite real-time and dynamic analysis of pyrethroid pesticides - Guojian Wu; Chenxing Du; Chuanyi Peng; Zitong Qiu; Si Li; Wenjuan Chen; Huimin Qiu; Zhi Zheng; Zhiwei Lu; Yizhong Shen (Journal of Hazardous Materials, 2024)

In-situ and ex-situ selective catalysis of biochar-based catalysts for the production of high-quality bio-oil and H2-rich gas from tobacco stem - Xin Tang; Xiang Yang Li; Qiu Fa He; Yao Peng; Bin Peng; Yu Zhang; Wei Luo; Zhi Zhou (Journal of Environmental Chemical Engineering, 2024)

Mode of action underlying toxicity of Camptothecin to Spodoptera frugiperda (Lepidoptera) larvae - Jun-li Lv; Wen-qing Lai; Lei Pang; Xiao-ying Zhang; Kai-yi Zheng; Qiang Zhang; Zhan-peng Lu; Zhi-sheng Wang; Fasihul Lisan; Xue-yang Wang; Lu-feng Hu; Ming-jie Deng (Journal of Asia-Pacific Entomology, 2024)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

Cation exchange strategy of ellagic acid-based microporous metal-organic framework for efficient CO2/N2 and CO2/CH4 separation - Chen-Ning Li; Zhi-Peng Tao; Lin Liu; Daqiang Yuan; Zheng-Bo Han (Chemical Engineering Journal, 2024)

High-level extracellular expression of phospholipase D by combinatorial fine-tuning strategy in Bacillus subtilis for efficient biosynthesis of phosphatidic acid - Peng Zhang; Xin-An Mao; Jin-Song Gong; Xiao-Li Kong; Chang Su; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Paris xuefengshanensis (Melanthiaceae) sp. nov. from central China with a distinctive phylogenetic placement in Paris - Zhi Wang; Jun Yang; Qi Tang; Shuai Peng; Jing Tian; Heng Li; Guang-Wan Hu (Plant Systematics and Evolution, 2024)

Genome Mining Analysis Uncovers the Previously Unknown Biosynthetic Capacity for Secondary Metabolites in Verrucomicrobia - Xue Di; Peng Li; Jingxuan Wang; Vincent Nowak; Shuai Zhi; Meiling Jin; Liwei Liu; Shan He (Marine Biotechnology, 2024)

Pollinator-mediated selection on flowering start and corolla tube length differed between mating systems in a primrose species - Zhao-Li Tong; Yong-Peng Cha; Yin-Mei Ma; Yun Wu; Zhi-Qiang Zhang (Evolutionary Ecology, 2024)

Jeotgalibacillus haloalkalitolerans sp. nov., a novel alkalitolerant and halotolerant bacterium, isolated from the confluence of the Fenhe River and the Yellow River - Ya-Fei Zhang; Yun-Lin Peng; Yong-Hui Xiao; Bing Yu; Ming-Yue Cao; Zhi-Ling Zhang; Le-Qun Huang; Yi Li (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Ionized copolyesters with pH-responsive degradability: Accelerated degradation in specific environments - Xiao Li; Wei-Zhen Zheng; Peng-Yuan Xu; Ze-Yang Zhang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Jun-Hui Ji; Ge-Xia Wang (Science of The Total Environment, 2024)

Effect of climate warming on subsurface temperature in basins with topography-driven groundwater flow - Yi-Peng Zhang; Xiao-Wei Jiang; Shemin Ge; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Lizhi Wang; Qing Liu; Li Wan (Journal of Hydrology, 2024)

Research and application of joint-constrained inversion of transient electromagnetic multivariate parameter - Jian-lei Guo; Yan-wei Hou; Xiong-wei Li; Zhi-peng Qi; Ke-rui Fan; Wen-han Li; Wei-hua Yao; Xiu Li (Journal of Applied Geophysics, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Mechanism of extracellular polymeric substance production and its contribution to anaerobic digestion foaming: Insights from cellular signalling - Wenjie Ye; Lei Li; Pingjin Yang; Zhi Zhang; Linpei Han; Ronghuan Yuan; Xuya Peng (Chemical Engineering Journal, 2024)

Structural design and electronic regulation of atomically dispersed Mo-S4 sites by second shell N species reconfiguration for intensifying hydrogen spillover - Guangxun Sun; Shihuan Liu; Hongfu Shi; Peng Xue; Junxi Li; Wenwen Gao; Feiyang Li; Fuliang Chen; Yanpeng Fu; Zhi Liu; Yuan Pan; Yunqi Liu (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Genomic Investigation of a Rhizosphere Isolate, Streptomyces sp. JL1001, Associated with Polygonatum cyrtonema Hua - Lin Jiang; Zixian Zeng; Zhi Wang; Min Tang; Sai Jiang; Qingxian Ma; Zhong Wang; Dian Peng; Shunxiang Li; Hong Pu (Current Microbiology, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Sustainable recycling of the biodegradable polyester poly(butylene succinate) via selective catalytic hydrolysis and repolymerization - Wei-Zhen Zheng; Xiao Li; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Jun-Hui Ji; Ge-Xia Wang (Resources, Conservation and Recycling, 2024)

Abundant small microplastics hidden in water columns of the Yellow Sea and East China Sea: Distribution, transportation and potential risk - Jia Lin; Jia-Yuan Zheng; Zhi-Geng Zhan; Yuan-Ming Zhao; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Water-soluble biodegradable polyesters with pH and ionic responsivity - Xiao Li; Wei-Zhen Zheng; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Yang Zhao; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

Na/Bi-co-doping and heterogeneous interfaces leading to enhanced thermoelectric performance of p-type Mg3Sb2-based Zintls - Zhe Xu; Xiao-Lei Shi; Yibo Zhang; Jisheng Liang; Meng Li; Chengyan Liu; Lei Miao; Siqi Liu; Shihao Wang; Qi Zhou; Jie Gao; Zhongwei Zhang; et al. (Chemical Engineering Journal, 2024)

Association Between Copper Intake and Migraine: a National Cross-sectional Study - Yiyan Sun; Zhi Jin; Junqing Zhang; Hongyun Wu; Xiaotong Li; Leiyong Zhao; Wei Peng (Biological Trace Element Research, 2024)

A preliminary result for centralized autonomous orbit determination of gnss constellation and lunar satellite based on inter-satellite link measurements - Peng Luo; Ye-Zhi Song; Jianhua Yang; Xiaogong Hu; Chengpan Tang; Kai Li; Qingfeng Wu (GPS Solutions, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Facile construction of pectin-based hesperidin microcapsules: Solubilization, stability, loading process, and release mechanism - Peng Zhou; Xiangzhou Li; Zhi Jiang; Jun Zhou; Liqun Shen (Food Chemistry, 2024)

Alteration of soil pH induced by submerging/drainage and application of peanut straw biochar and its impact on Cd(II) availability in an acidic soil to indica-japonica rice varieties - Md Romel Biswash; Ke-wei Li; Ren-kou Xu; Ernest Uwiringiyimana; Peng Guan; Hai-long Lu; Jiu-yu Li; Jun Jiang; Zhi-neng Hong; Ren-yong Shi (Environmental Pollution, 2024)

The mechanism of interaction between tri-para-cresyl phosphate and human serum protein: A multispectroscopic and in-silico study - Shang-Chun Li; Han Xu; Peng-Fei Wang; Li-Mei Wang; Yue-Rou Du; Yong-Bin Guan; Zhi-Xia Han; Qing-Bi Zhang (Chemico-Biological Interactions, 2024)

Development of polysaccharide-coated layered double hydroxide nanocomposites for enhanced oral insulin delivery - Huiwen Pang; Youzhi Wu; Yang Chen; Chen Chen; Xuqiang Nie; Peng Li; Guojun Huang; Zhi Ping Xu; Felicity Y. Han (Drug Delivery and Translational Research, 2024)
Oral insulin (INS) is predicted to have the most therapeutic advantages in treating diabetes to repress hepatic glucose production through its potential to mimic the endogenous insulin pathway. Many oral insulin delivery systems have been investigated. Layered double hydroxide (LDH) as an inorganic material has been widely used in drug delivery thanks to its appealing features such as good biocompatibility, low toxicity, and excellent loading capability. However, when used in oral drug delivery, the effectiveness of LDH is limited due to the acidic degradation in the stomach. In this study, to overcome these challenges, chitosan (Chi) and alginate (Alg) dual-coated LDH nanocomposites with the loading of insulin (Alg-Chi-LDH@INS) were developed by the layered-by-layered method for oral insulin delivery with dynamic size of ~ 350.8 nm, negative charge of ~ − 13.0 mV, and dispersity index 0.228. The insulin release profile was evaluated by ultraviolet–visible spectroscopy. The drug release profiles evidenced that alginate and chitosan coating partially protect insulin release from a burst release in acidic conditions. The analysis using flow cytometry showed that chitosan coating significantly enhanced the uptake of LDH@INS by Caco-2 cells compared to unmodified LDH and free insulin. Further in the in vivo study in streptozocin-induced diabetic mice, a significant hypoglycemic effect was maintained following oral administration with great biocompatibility (~ 50% blood glucose level reduction at 4 h). This research has thus provided a potential nanocomposite system for oral delivery of insulin. Graphical Abstract

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Discrimination and prediction of Qingzhuan tea storage year using quantitative chemical profile combined with multivariate analysis: Advantages of MRMHR based targeted quantification metabolomics - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

Fabrication of a label-free electrochemical immunosensor by functionalized nanofiber membrane for the ultrasensitive detection of quinalphos - Jian-cheng Hu; Peng Wen; Yu Wang; Jin-yi Yang; Zhi-li Xiao; Zhen-lin Xu; Yu-dong Shen; Hong Wang; Bruce D. Hammock (Food Control, 2024)

Teleost-specific TLR23 in Takifugu rubripes recruits MyD88 to trigger ERK pathway and promotes antibacterial defense - Yu-ting Du; Hong-qiang Zhang; Yan Li; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Fish & Shellfish Immunology, 2024)

Erosion, deposition and breach evolution of landslide dams composed of various dam material types based on flume tests - Chenyi Ma; Ming Peng; Limin Zhang; Zhenming Shi; Jiawen Zhou; Hongxin Chen; Yan Zhu; Zhi Li (Engineering Geology, 2024)

Numerical modelling of sand liquefaction via a weakly coupled approach between lattice spring and discrete element methods - Zhe Li; Gao-Feng Zhao; Yu-Jie Zhang; Zhi-Peng Hao; Kai-Li Niu; Run Liu (Computers and Geotechnics, 2024)

Response of soil aggregate-associated fertility and microbial communities to afforestation in the degraded ecosystem of the Danjiangkou Reservoir, China - Peng Chen; Li Wang; Jun-Ya Li; Wenjie Wan; Run-Qin Zhang; Yi Liu; Zhi-Guo Li (Plant and Soil, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

How is about the flash drought events and their impacts on vegetation in Central Asia - Yanchao Zhu; Peng Yang; Heqing Huang; Jun Xia; Yaning Chen; Zhi Li; Xiaorui Shi (Climate Dynamics, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Daphmacrimines A−K, Daphniphyllum alkaloids from Daphniphyllum macropodum Miq - Li-Li Xu; Zhen-Peng Niu; Duo-Zhi Chen; Yu Zhang; Qian Zhao; Hong Liang; Sheng Li; Jin-Liang Li; Xiao Ding; Chong-Lin Yang; Xiao-Jiang Hao (Phytochemistry, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Large-scale and facile fabrication of phenyl-containing silicone foam materials with lightweight, wide-temperature flexibility and tunable pore structure for exceptional thermal insulation - Yu-Yue Wu; Zhi-Hao Wu; Zuan-Yu Chen; Li-Dong Peng; Zi-Qi Guan; Yang Li; Cheng-Fei Cao; Guo-Dong Zhang; Jie-Feng Gao; Pingan Song; Yong-Qian Shi; Long-Cheng Tang (Chemical Engineering Journal, 2024)

RETRACTED: A chitosan-camouflaged nanomedicine triggered by hierarchically stimuli to release drug for multimodal imaging-guided chemotherapy of breast cancer - Pei Wang; Zhi Peng; Yanyan Zhang; Xuejing Zhang; Xia Chen; Fan Li; Bo Chen; Shiwei Niu; Kaili Du; Li-Min Zhu (Carbohydrate Polymers, 2024)

Genome-wide association studies dissect low-phosphorus stress response genes underling field and seedling traits in maize - Bowen Luo; Guidi Zhang; Ting Yu; Chong Zhang; Guohui Yang; Xianfu Luo; Shuhao Zhang; Jianyong Guo; Haiying Zhang; Hao Zheng; Zirui Tang; Qile Li; et al. (Theoretical and Applied Genetics, 2024)

Exploring the phosphorus–starch content balance mechanisms in maize grains using GWAS population and transcriptome data - Bowen Luo; Haiying Zhang; Zheng Han; Xiao Zhang; Jianyong Guo; Shuhao Zhang; Xianfu Luo; Jin Zhao; Wei Wang; Guohui Yang; Chong Zhang; Jing Li; et al. (Theoretical and Applied Genetics, 2024)

Colonization ability and uniformity of resources and environmental factors determine biological homogenization of soil protists in human land‐use systems - Zhi‐Peng Li; Hua‐Yuan Shangguan; Haifeng Yao; Xiao‐Ru Yang; Yuri Mazei; Biao Zhu; Stefan Scheu; Xin Sun (Global Change Biology, 2024)
Humans have substantially transformed the global land surface, resulting in the decline in variation in biotic communities across scales, a phenomenon known as “biological homogenization.” However, different biota are affected by biological homogenization to varying degrees, but this variation and the underlying mechanisms remain little studied, particularly in soil systems. To address this topic, we used metabarcoding to investigate the biogeography of soil protists and their prey/hosts (prokaryotes, fungi, and meso‐ and macrofauna) in three human land‐use ecosystem types (farmlands, residential areas, and parks) and natural forest ecosystems across subtropical and temperate regions in China. Our results showed that the degree of community homogenization largely differed between taxa and functional groups of soil protists, and was strongly and positively linked to their colonization ability of human land‐use systems. Removal analysis showed that the introduction of widespread, generalist taxa (OTUs, operational taxonomic units) rather than the loss of narrow‐ranged, specialist OTUs was the major cause of biological homogenization. This increase in generalist OTUs seemingly alleviated the negative impact of land use on specialist taxa, but carried the risk of losing functional diversity. Finally, homogenization of prey/host biota and environmental conditions were also important drivers of biological homogenization in human land‐use systems, with their importance being more pronounced in phagotrophic than parasitic and phototrophic protists. Overall, our study showed that the variation in biological homogenization strongly depends on the colonization ability of taxa in human land‐use systems, but is also affected by the homogenization of resources and environmental conditions. Importantly, biological homogenization is not the major cause of the decline in the diversity of soil protists, and conservation and study efforts should target at taxa highly sensitive to local extinction, such as parasites.

Identification of UDP-glucuronosyltransferase (UGT) isoforms involved in the metabolism of Chlorophenols (CPs) - Kai Yang; Ruo-Yong Jia; Xiao-Song Li; Shao-You Lu; Jian-Jun Liu; Zhi-Peng Zhang; Zhong-Ze Fang (Chemosphere, 2024)

A novel approach and mechanistic insight into the co-extraction of essential oil and pectin from Citrus aurantium L. var. amara Engl. based on machine learning and DFT calculations - Peng Zhou; Xiangzhou Li; Ying Lu; Zhi Jiang; Liqun Shen (Sustainable Chemistry and Pharmacy, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

A meta-analysis of antibiotic residues in the Beibu Gulf - Hong-zhi Tang; Tianyu Zhao; Qun-jian Yin; Peng-fei Zheng; Fang-chao Zhu; Hong-yong Tang; An-qi Li (Marine Environmental Research, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Drought propagation and its driving forces in central Asia under climate change - Yanchao Zhu; Peng Yang; Jun Xia; Heqing Huang; Yaning Chen; Zhi Li; Kaiya Sun; Jingxia Song; Xiaorui Shi; Xixi Lu (Journal of Hydrology, 2024)

Effects of Continuous Cropping and Application of Bio-organic Fertilizers on Growth, Yield and Quality of Sugar Beet under Reduced Chemical Fertilizer Application - Xiaoxia Guo; Lu Tian; Yinghao Li; Baiquan Song; Chunyan Huang; Zhi Li; Peng Zhang; Caiyuan Jian; Kang Han; Dejuan Kong; Zhenzhen Wang; Jia Liu; et al. (Sugar Tech, 2024)

A small landslide induced a large disaster prior to the heavy rainy season in Jinkouhe, Sichuan, China: characteristics, mechanism, and lessons - Runing Hou; Zhi Li; Weihao Ye; Taixin Peng; Shufeng Tian; Ningsheng Chen; Na Huang; Marcelo Somos-Valenzuela (Landslides, 2024)

Co4+ in porous ZIF-67-derives intercalating-bridging adsorption of 2-reaction sites for simultaneous 2-electron transfer toward sensitive detection of uric acid - Li Peng Gan; Juan Li; Fan Shi; Zhuo Zou; Ke Jiang Li; Zhuan Zhuan Shi; Xiao Shuai Wu; Yun Peng Li; Wei Sun; Zhi Song Lu; Tao Hu; Liming Dai; et al. (Analytica Chimica Acta, 2024)

Mechanically treated Mn2O3 triggers peracetic acid activation for superior non-radical oxidation of micropollutants: Identification of reactive complexes - Yudan Dong; Chuan-Shu He; Si Sun; Jiali Liu; Zhi-Hui Xie; Jie-Yuan Li; Peng Zhou; Heng Zhang; Fan Dong; Bo Lai (Water Research, 2024)

Anthropogenic factors explain urban plant diversity across three tropical cities in China - Lin-Yuan Guo; Mir Muhammad Nizamani; AJ Harris; Josep Padullés Cubino; Joel B. Johnson; Jian-Peng Cui; Hai-Li Zhang; Jing-Jiang Zhou; Zhi-Xin Zhu; Hua-Feng Wang (Urban Forestry & Urban Greening, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Microbial mechanisms in nitrogen fertilization: Modulating the re-mobilization of clay mineral-bound cadmium in agricultural soils - Jun-Feng Wang; Can Liu; Zhi-Min Xu; Fo-Peng Wang; Yun-Yun Sun; Jia-Wei Huang; Qu-Sheng Li (Science of The Total Environment, 2024)

Multilayered Fe3O4@(ZIF-8)3 combined with a computer-vision-enhanced immunosensor for chloramphenicol enrichment and detection - Puyue Liu; Yiming Dong; Xiaoxuan Li; Yu Zhang; Zhi Liu; Yingying Lu; Xuewen Peng; Ruifang Zhai; Yiping Chen (Journal of Hazardous Materials, 2024)

Microplastics in remote coral reef environments of the Xisha Islands in the South China Sea: Source, accumulation and potential risk - Jia Lin; Yuan-Ming Zhao; Zhi-Geng Zhan; Jia-Yuan Zheng; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Identification of particle distribution pattern in vertical profile via unmanned aerial vehicles observation - Zhi-Heng Chen; Bo-Wen Li; Bai Li; Zhong-Ren Peng; Hai-Chao Huang; Jun-Qi Wu; Hong-Di He (Environmental Pollution, 2024)

Quantification and uncertainty of global upland soil methane sinks: Processes, controls, model limitations, and improvements - Hanxiong Song; Changhui Peng; Qiuan Zhu; Zhi Chen; Jean-Pierre Blanchet; Qiuyu Liu; Tong Li; Peng Li; Zelin Liu (Earth-Science Reviews, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Nitazoxanide protects against experimental ulcerative colitis through improving intestinal barrier and inhibiting inflammation - Hu-Tai-Long Zhu; Jing Luo; Yi Peng; Xiao-Fan Cheng; Shang-Ze Wu; Yin-Di Zhao; Le Chang; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2024)

Initial study and phylogenetic analysis of hard ticks (Acari: Ixodidae) in Nantong, China along the route of avian migration - Jian-Ming Yuan; Jing Su; Zhi-Hai Zhang; Bin Sun; Xue-Li Jiao; Xin Zhang; Yun-Peng Zhai; Yu-Jie Chen (Experimental and Applied Acarology, 2024)

Synthesis and Application of Specific N2H4 Fluorescent Probes with AIE Effect Based on Pyrazole Structure - Yun-Shang Yang; Zhen Zhang; Ying-Peng Zhang; Yu-Ning Liang; Xing-Xing Li; Zhi-Dong Teng (Journal of Fluorescence, 2024)

A novel method for identifying aerobic granular sludge state using sorting, densification and clarification dynamics during the settling process - Zhi-Hua Li; Ruo-Lan Wang; Meng Lu; Xin Wang; Yong-Peng Huang; Jia-Wei Yang; Tian-Yu Zhang (Water Research, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Efficient removal of tetracycline hydrochloride through novel Fe/BiOBr/Bi2WO6 photocatalyst prepared by dual-strategy under visible-light irradiation - Guanlong Yu; Kai Yang; Yi Yang; Yifu Li; Qifang Sun; Peiyuan Li; Wenming Wang; Fengming Song; Tao Ling; Xuejun Peng; Zhi Yu; Shiquan Sun (Journal of Environmental Sciences, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Genomic data and ecological niche modeling reveal an unusually slow rate of molecular evolution in the Cretaceous Eupteleaceae - Kun-Li Xiang; Sheng-Dan Wu; Lian Lian; Wen-Chuang He; Dan Peng; Huan-Wen Peng; Xiao-Ni Zhang; Hong-Lei Li; Jia-Yu Xue; Hong-Yan Shan; Gui-Xia Xu; Yang Liu; et al. (Science China Life Sciences, 2024)

Differential detection of H1N1 virus spiker proteins by two hexaphenylbutadiene isomers based on size-matching principle - Xiaoling Pan; Jian Wang; Kai Zhang; Peng Sun; Jianbing Shi; Junge Zhi; Zhengxu Cai; Zi Li; Dayan Wang; Bin Tong; Yuping Dong (Analytica Chimica Acta, 2024)

Boron deficiency energizes cyanide uptake and assimilation through activating plasma membrane H+-ATPase in rice plants - Cheng-Zhi Li; Abid Ullah; Peng Tian; Xiao-Zhang Yu (Chemosphere, 2024)

The infectious haemorrhagic syndrome virus (IHSV) from rice-field eel (Monopterus albus): Isolation, genome sequence, cross-infection and induced-immune response in Chinese perch (Siniperca chuatsi) - Shan Nan Chen; Hui Jun Huo; Yong Jin; Xue Yun Peng; Bo Li; Xiang Yang Wu; Zhi Wei Zhang; Jing Yun Tian; Qian Wang; Nan Li; Lan Hao Liu; P. Nie (Aquaculture, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Performance assessment of solar photovoltaic-based constructed wetland for sustainable rural wastewater treatment - Ye Yang; Chao-Kun Li; Liu Han; Zhi-Peng Yang; Ning-Ning Xiao; Nan Zhang; Ying-Ying Dong; Zhi-Wen Chen; Hui Xi; Wen-Dong Wang (Journal of Water Process Engineering, 2024)

Pumping-induced groundwater aging and rejuvenation in aquifer-aquitard systems: A perspective from regional groundwater flow - Yi-Peng Zhang; Xiao-Wei Jiang; Xiao-Lang Zhang; Zhi-Yuan Zhang; Xu-Sheng Wang; Guo-Liang Cao; Wen Wei; Li Wan (Journal of Hydrology, 2024)

Biodegradation of polyethylene terephthalate by Tenebrio molitor: Insights for polymer chain size, gut metabolome and host genes - Lei He; Shan-Shan Yang; Jie Ding; Cheng-Xin Chen; Fan Yang; Zhi-Li He; Ji-Wei Pang; Bo-Yu Peng; Yalei Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Journal of Hazardous Materials, 2024)

Impact of deoxynivalenol on rumen function, production, and health of dairy cows: Insights from metabolomics and microbiota analysis - Jia-nan Dong; Zhi-kun Zhao; Zhan-qing Wang; Song-ze Li; Yong-peng Zhang; Zhe Sun; Gui-xin Qin; Xue-feng Zhang; Wei Zhao; Natnael Demelash Aschalew; Tao Wang; Yu-guo Zhen (Journal of Hazardous Materials, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Enhanced delignification and production of bioactive compounds in wheat straw by optimizing sterilization methods for Irpex lacteus fermentation - Peng Zhu; Dongze Niu; Sainan Zhang; Chunyu Li; Dongmin Yin; Junqiang Zhi; Lili Zhang; Xingmei Jiang; Jianjun Ren (Food Chemistry, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Exposure to pesticides and risk of colorectal cancer: A systematic review and meta-analysis - Pin-Peng Xie; Zhi-Qiang Zong; Jian-Chao Qiao; Zhuo-Yan Li; Cheng-Yang Hu (Environmental Pollution, 2024)

Multinational dynamic steel cycle analysis reveals sequential decoupling between material use and economic growth - Xue Yang; Chao Zhang; Xinyi Li; Zhi Cao; Peng Wang; Heming Wang; Gang Liu; Ziqian Xia; Dajian Zhu; Wei-Qiang Chen (Ecological Economics, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Correlation of Gut Microbiota with Children Obesity and Weight Loss - Li-Jun Peng; Yan-Ping Chen; Fang Qu; Yan Zhong; Zhi-Sheng Jiang (Indian Journal of Microbiology, 2024)

Natural variation of Grain size 3 allele differentially functions in regulating grain length in xian/indica and geng/japonica rice - Yong-Bin Peng; Chen-Yang Du; Ya-Nan He; Chong-Ke Zheng; Wei Sun; Jin-Jun Zhou; Li-Xia Xie; Cong-Hui Jiang; Jian-Di Xu; Fang Wang; Xian-Zhi Xie (Euphytica, 2024)

Three-dimensional inter-basin groundwater flow toward a groundwater-fed stream: Identification, partition, and quantification - Peng-Fei Han; Xu-Sheng Wang; Yangxiao Zhou; Zhi Yang; Li Wan; Jinsong Chen; Xiao-Wei Jiang (Journal of Hydrology, 2024)

Characteristics of ash formed by different lubricant additives and its effect on DPF performance - Pi-qiang Tan; Tian-peng Liu; Li-shuang Duan; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Effects of wax on the formation of methane hydrate in oil-dominate systems: Experiments and molecular dynamics simulations - Limin Wang; Xin Zheng; Peng Xiao; Xing Huang; Bei Liu; Zhi Li; Guangjin Chen; Changyu Sun (Fuel, 2024)

UHPLC-QTOF-MS-based untargeted metabolomic authentication of Chinese red wines according to their grape varieties - Xiao-Li Yin; Zhi-Xin Peng; Yuan Pan; Yi Lv; Wanjun Long; Hui-Wen Gu; Haiyan Fu; Yuanbin She (Food Research International, 2024)

Revitalizing mitochondrial function and empowering spinal cord recovery using copper-catalyzed Pdots - Bao-Feng Zhao; Fan Wang; Jia-Chen Sun; Jin-Peng Gao; Li-Juan Zhao; Zhao-Liang Shen; Zhi-Peng Li; Yi-Xuan Wang; Yuan Wang; Dan Li; Xi-Fan Mei (Chemical Engineering Journal, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

A Novel Multi-Functional Fluorescence Probe for the Detection of Al3+/Zn2+/Cd2+ and its Practical Applications - Jing Fan; Xiao-Meng Liu; Peng Sun; Huan Su; Yan Sun; Qing-Zhong Li; Cheng-Zhi Xie; Jing-Yuan Xu (Journal of Fluorescence, 2024)

Managing stability of aerobic granules by coordinating diameter and denitrification - Yong-Peng Huang; Xin Wang; Ruo-Lan Wang; Jin-Tao He; Yuan Huang; Zhen-Yu Hang; Xi Chen; Zhi-Hua Li (Science of The Total Environment, 2024)

Novel α-amino acid-like structure decorated biochar for heavy metal remediation in acid soil - Shikai Li; Yujiao Wen; Yifan Wang; Meng Liu; Lezhu Su; Zhengjie Peng; Zhi Zhou; Nan Zhou (Journal of Hazardous Materials, 2024)

Effects of lubricant components on ash-bridge deposition characteristics in the diesel particulate filter - Pi-qiang Tan; Yuan Tian; Li-shuang Duan; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Urban greenspaces shape soil protist communities in a location-specific manner - Hua-Yuan Shangguan; Stefan Geisen; Zhi-Peng Li; Hai-Feng Yao; Gang Li; Martin F. Breed; Stefan Scheu; Xin Sun (Environmental Research, 2024)

Sources of atmospheric oxygenated volatile organic compounds in different air masses in Shenzhen, China - Zhi-Jie Li; Ling-Yan He; Hao-Nan Ma; Xing Peng; Meng-Xue Tang; Ke Du; Xiao-Feng Huang (Environmental Pollution, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Feasibility of vertical force–velocity profiles to monitor changes in muscle function following different fatigue protocols - Zhaoqian Li; Peng Zhi; Zhi Yuan; Amador García-Ramos; Mark King (European Journal of Applied Physiology, 2024)

GRACE-based dynamic assessment of hydrological drought trigger thresholds induced by meteorological drought and possible driving mechanisms - Zhiming Han; Shengzhi Huang; Jian Peng; Jianfeng Li; Guoyong Leng; Qiang Huang; Jing Zhao; Fang Yang; Panxing He; Xiaoyu Meng; Zhi Li (Remote Sensing of Environment, 2023)

Numerical simulation of hydrodynamic performance of pump-jet propulsor with serrated trailing-edge duct under different working conditions - Yu Sun; Li-xin Qu; Huang-hua Peng; Jia-min Guo; Zhi-xin Xiong (Ocean Engineering, 2023)

Physicochemical characteristics of ash-bridges in diesel particulate filter - Li-shuang Duan; Pi-qiang Tan; Yun-peng Li; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Silver metallization-triggered liposome-embedded AIE fluorophore for dual-mode detection of biogenic amines to fight food freshness fraud - Xiang Gao; Peng Nie; Peiran Li; Zhi Zheng; Jieshun Cheng; Ying Gu; Yizhong Shen (Food Chemistry, 2023)

Metabolome and Transcriptome Association Analysis Reveals the Link Between Pigmentation and Nutrition Utilization in the Juveniles of Sea Cucumber Holothuria leucospilota - Jiasheng Huang; Zixuan E; Wenjie Pan; Zhi Li; Tiehao Lin; Chunhua Ren; Peng Luo; Bo Ma; Yang Liu; Xugan Wu; Chaoqun Hu; Xiao Jiang; et al. (Marine Biotechnology, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Land use decouples parasite–metazoan host biodiversity associations in soils across subtropical and temperate zones in China - Zhi‐Peng Li; Stefan Geisen; Hua‐Yuan Shangguan; Alexei V. Tiunov; Stefan Scheu; Yong‐Guan Zhu; Xin Sun (Global Ecology and Biogeography, 2023)
Aim Soils harbour a large number of unicellular eukaryotic parasites of metazoans, particularly Apicomplexa. Apicomplexan distribution, their associations with hosts, and impacts of human‐dominated land use are little studied. We aimed to fill this gap by a biodiversity survey across large spatial scales. Location China. Time period May to September 2021. Major taxa studied Soil Apicomplexa and Metazoa Methods We used metabarcoding to investigate the biogeography of and links between Apicomplexa and soil Metazoa in three human‐dominated ecosystem types (farmlands, residential areas and parks) and more natural forest ecosystems across subtropical, warm‐temperate and mid‐temperate climatic regions in China. Results Human‐dominated land use indirectly reduced apicomplexan taxon richness by reducing metazoan taxon richness. However, the richness reduction of parasites was generally more pronounced in subtropical and mid‐temperate regions than in the warm‐temperate region. Mechanisms driving the richness reduction of parasites also differed between climatic regions, with the reduction in the subtropical region less related to the decrease in metazoan richness than in the mid‐temperate region. Human‐dominated ecosystems reduced richness associations between parasites and Metazoa, and this disrupted the cascading effect of climatic factors from metazoan to parasite communities. Moreover, co‐occurrence analyses showed that metazoan taxa more abundant in human‐dominated land‐use systems with dryer and hotter conditions were less likely associated with apicomplexan taxa. Main conclusions We conclude that decreased host taxon richness is an important, but not the only driver of reduced parasite taxon richness in soil systems. Apicomplexan richness was largely decoupled from metazoan richness in human‐dominated ecosystems, which emphasizes the important role of human activities in rewiring fundamental ecological patterns with global change. Overall, the results advance our understanding of principle characteristics of and interactions in soil communities, and their response to human activities, especially agriculture and urbanization.

Adsorption-desorption behaviors of ciprofloxacin onto aged polystyrene fragments in aquatic environments - Xiao-Yang Liu; Ning Wang; Long-Yi Lv; Peng-Fei Wang; Wen-Fang Gao; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemosphere, 2023)

Soil aggregate-associated organic carbon mineralization and its driving factors in rhizosphere soil - Jun-Ya Li; Peng Chen; Zhi-Guo Li; Lin-Yang Li; Run-Qin Zhang; Wei Hu; Yi Liu (Soil Biology and Biochemistry, 2023)

All-natural environmentally degradable poly (butylene terephthalate-co-caprolactone): A theoretical and experimental study of its degradation properties and mechanisms - Peng-Yuan Xu; Ping-Li Wang; Tian-Yuan Liu; Zhi-Chao Zhen; Bo Lu; Dan Huang; Ge-Xia Wang; Jun-Hui Ji (Science of The Total Environment, 2023)

Phylotranscriptomic analyses reveal deep gene tree discordance in Camellia (Theaceae) - Qiong Zhang; Ryan A. Folk; Zhi-Qiong Mo; Hang Ye; Zhao-Yuan Zhang; Hua Peng; Jian-Li Zhao; Shi-Xiong Yang; Xiang-Qin Yu (Molecular Phylogenetics and Evolution, 2023)

Interaction of focused recharge and deep groundwater discharge near a wetland: A study in the Ordos Basin, China - Jia-Xin Shi; Xiao-Wei Jiang; Zhi-Yuan Zhang; Yi-Peng Zhang; Xu-Sheng Wang; Li Wan (Journal of Hydrology, 2023)

Effect of ash on temperature and particulate emission characteristics of diesel particulate filter during active regeneration - Li-shuang Duan; Pi-qiang Tan; Yi-fan Yin; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Carbon-efficient production planning for long-chain integrated refinery-petrochemical processes: A material-energy-carbon optimization perspective - Tingwei Zhang; Feifei Shen; Xin Peng; Zhi Li; Weimin Zhong (Journal of Cleaner Production, 2023)

Stability evaluation of salt cavern hydrogen storage and optimization of operating parameters under high frequency injection production - De-Peng Li; Wei Liu; Pan Fu; Lin Li; Fan-Sheng Ban; Qi-Hang Li; Jin-Yang Fan; De-Yi Jiang; Zhi-Xin Zhang (Gas Science and Engineering, 2023)

Insights into the effect of extracellular polymeric substances on anaerobic digestion foaming: From perspectives of composition, hydrophobicity, and functional groups - Pingjin Yang; Lei Li; Yingyue Zhou; Shangyi Zhang; Zhi Zhang; Yun Peng; Hengyi Liu; Wenjie Ye; Xuya Peng (Chemical Engineering Journal, 2023)

Amino-terminated carbon dots for imaging Golgi apparatus polarity in live cells - Lei Zhan; Peng Hou; Na Chen; Yuan Fang Li; Chun Mei Li; Cheng Zhi Huang (Chemical Engineering Journal, 2023)

Enhancement patterns of potassium on nitrogen transport and functional genes in cotton vary with nitrogen levels - Peng Chen; Linyang Li; Shujie Xia; Runhua Zhang; Runqin Zhang; Xiao-Min Zeng; Du Shuai; Yi Liu; Zhi-Guo Li (Plant Science, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

A functionalized ionic compound for the extraction of ReO4−/TcO4− from highly acidic environment - Xupeng Zhi; Yinglin Shen; Peng Liu; Meiying Liu; Xiaomin Li; Yiwei Huang; Xinlong Chen; Fei Wu (Journal of Water Process Engineering, 2023)

Copper enhanced arsenic-accumulation in As-hyperaccumulator Pteris vittata by upregulating its gene expression for As uptake, translocation, and sequestration - Chen-Jing Liu; You-Jing Peng; Chun-Yan Hu; Si-Xue He; Shu-Fen Xiao; Wei Li; Song-Ge Deng; Zhi-Hua Dai; Lena Q. Ma (Journal of Hazardous Materials, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Sustainable fabrication of zwitterionic nanofiltration membranes with enhanced antifouling performance using sugar - Siew Kei Lau; Tian-Zhi Jia; Xue-Li Cao; Shi-Peng Sun; Wai Fen Yong (Journal of Environmental Chemical Engineering, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Identification of Molecular Markers for Fertility in Sugar Beet - Fei Peng; Shengnan Li; Zhi Pi; Zedong Wu (Sugar Tech, 2023)

Mechanical Behavior and Fracture Evolution Mechanism of Composite Rock Under Triaxial Compression: Insights from Three-Dimensional DEM Modeling - Yu Song; Sheng-Qi Yang; Ke-Sheng Li; Peng-Fei Yin; Peng-Zhi Pan (Rock Mechanics and Rock Engineering, 2023)

Identification of a novel Carassius amphitetraploid clone and its transcriptomic responses to herpesvirus infection - Xiao-Li Yang; Yang Wang; Zhi Li; Peng Yu; Meng Lu; Xi-Yin Li; Zhong-Wei Wang; Xiao-Juan Zhang; Jian-Fang Gui; Li Zhou (Aquaculture, 2023)

Serum levels of IL-6/IL-10/GLDH may be early recognition markers of anti-tuberculosis drugs (ATB) -induced liver injury - Huai-Rong Xiang; Yun Li; Xuan Cheng; Bei He; Hua-Min Li; Qi-Zhi Zhang; Bin Wang; Wen-Xing Peng (Toxicology and Applied Pharmacology, 2023)

One-stage partial nitrification/anammox system with short sludge retention time and low mixed liquor suspended solids long-term control: Establishment, performance and sludge characteristics - Cong Wang; Li-Fang Liu; Shu-Jun Zhang; Zhi-Ming Qu; Wei-Kang Qi; Yong-Zhen Peng (Science of The Total Environment, 2023)

Inoculation of Escherichia coli enriched the key functional bacteria that intensified cadmium accumulation by halophyte Suaeda salsa in saline soils - Tao He; Zhi-Min Xu; Jun-Feng Wang; Ke Zhang; Fo-Peng Wang; Wan-Li Li; Ping Tian; Qu-Sheng Li (Journal of Hazardous Materials, 2023)

Adaptive management of water resources system in the arid Aksu river basin, northwest China - Peng Yang; Yanchao Zhu; Xiaoyan Zhai; Jun Xia; Yaning Chen; Heqing Huang; Zhi Li; Xiaorui Shi; Libo Zhou; Cai Fu (Journal of Cleaner Production, 2023)

Synthesis and characterization of Ag@Cu-based MOFs as efficient adsorbents for iodine anions removal from aqueous solutions - Chun-Hui Gong; Zhi-Ying Li; Kai-Wei Chen; Ao-Tian Gu; Peng Wang; Yi Yang (Journal of Environmental Radioactivity, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

Quantum computer-aided design for advanced superconducting qubit: Plasmonium - Feng-Ming Liu; Can Wang; Ming-Cheng Chen; He Chen; Shao-Wei Li; Zhong-Xia Shang; Chong Ying; Jian-Wen Wang; Yong-Heng Huo; Cheng-Zhi Peng; Xiaobo Zhu; Chao-Yang Lu; et al. (Science Bulletin, 2023)

Metamorphic P–T evolution of the pelitic granulites from the Helanshan in the North China Craton revealed by phase equilibrium modeling and garnet trace elements: Implications for Paleoproterozoic collisional orogenesis - Xiao-Fei Xu; Long-Long Gou; Yun-Peng Dong; Cheng-Li Zhang; Xiao-Ping Long; Yu-Hang Zhao; Feng Zhou; Zhi-Bo Tian (Precambrian Research, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

Ecological risk assessment and restoration area identification of Pengyang County on the basis of the landscape pattern and function - Xinghua Li; Zemin Ai; Zhi Yang; Yuyan Yao; Zhengyan Ren; Mengjia Hou; Jiayi Li; Xiaoshu Cao; Peng Li; Donghai Zhang; Ting Li; Xiaohu Dang (Environmental Monitoring and Assessment, 2023)

Experimental investigation of damage evolution and fracture mechanism in rocks with a single flaw under stepwise cyclic compression - Shuting Miao; Peng-Zhi Pan; Amin Hekmatnejad; Yuxin Li (Bulletin of Engineering Geology and the Environment, 2023)

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

An online intelligent management method for wastewater treatment supported by coupling data-driven and mechanism models - Jian-Hui Wang; Du-Jiang Zhao; Wan-Shan Liao; Mohamed S. Mahmoud; Zhi-Wei Guo; Hui-Min Li; Xu Gao; Dong Feng; Long-Fei Shi; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2023)

Fluorescence tracing the degradation process of biodegradable PBAT: Visualization and high sensitivity - Tian-Yuan Liu; Zhi-Chao Zhen; Xiao-Ling Zang; Peng-Yuan Xu; Ge-Xia Wang; Bo Lu; Fei Li; Ping-Li Wang; Dan Huang; Jun-Hui Ji (Journal of Hazardous Materials, 2023)

Insights into the modulation of the multi-scale structure of glutelin on the textural properties of reconstituted rice - Li-Shuang Wang; Xiao-Shuai Yu; Ke-Xin Wang; Jin-Jie Huo; Xiao-Qi Ma; Yu-Min Duan; Zhi-Gang Xiao; Peng Wang (Innovative Food Science & Emerging Technologies, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Comparison of the cross-protection of PPRSV sublineage 8.7 MLV vaccines against the recombinant NADC30-like strain - Jianda Li; Kai Meng; Yu Wang; Zhao Wang; Jun Peng; Sufang Ren; Yuyu Zhang; Lihui Guo; Fei Liu; Tingting Lv; Jian Jiao; Yanyan Liu; et al. (Veterinary Microbiology, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

A clean two-stage Bayer process for achieving near-zero waste discharge from high-iron gibbsitic bauxite - Guo-tao Zhou; Yi-lin Wang; Yu-guan Zhang; Tian-gui Qi; Qiu-sheng Zhou; Gui-hua Liu; Zhi-hong Peng; Xiao-bin Li (Journal of Cleaner Production, 2023)

Rice husk biochar mediated red phosphorus for photocatalysis and photothermal removal of E. coli - Meng Liu; Liqian Guan; Yujiao Wen; Lezhu Su; Zhan Hu; Zhengjie Peng; Shikai Li; Qiyuan Tang; Zhi Zhou; Nan Zhou (Food Chemistry, 2023)

Rapid identification of high and low cadmium (Cd) accumulating rice cultivars using machine learning models with molecular markers and soil Cd levels as input data - Zhong Tang; Ting-Ting You; Ya-Fang Li; Zhi-Xian Tang; Miao-Qing Bao; Ge Dong; Zhong-Rui Xu; Peng Wang; Fang-Jie Zhao (Environmental Pollution, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

The effects of serotonergic psychedelics in synaptic and intrinsic properties of neurons in layer II/III of the orbitofrontal cortex - Zi-Hang Tang; Zhi-Peng Yu; Qiong Li; Xiao-Qin Zhang; Kadeliya Muhetaer; Zheng-Chun Wang; Peng Xu; Hao-Wei Shen (Psychopharmacology, 2023)

Numerical simulation of rockburst disaster and control strategy of constant resistance and large deformation anchor cable in Gaoloushan tunnel - Cheng-yu Miao; Ming Jiang; Zhi-hu Li; Xiao-ming Sun; Tong Zhang; Yong Zhang; Jin-kun Yang; Chao Ren; Peng Song (Journal of Mountain Science, 2023)

Wireless remote spatiotemporal monitoring of high-fill foundation deformation - Xiao-hui Yang; Zhi-qian Li; Yan-peng Zhu; Nan Guo (Journal of Mountain Science, 2023)

Retraction Note to: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2023)

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

An efficient approach to synthesize sterile allopolyploids through the combined reproduction mode of ameiotic oogenesis and sperm-egg fusion in the polyploid Carassius complex - Meng Lu; Qin-Can Zhang; Zi-Yu Zhu; Fang Peng; Zhi Li; Yang Wang; Xi-Yin Li; Zhong-Wei Wang; Xiao-Juan Zhang; Li Zhou; Jian-Fang Gui (Science Bulletin, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Dynamic evolution of recent droughts in Central Asia based on microwave remote sensing satellite products - Peng Yang; Jun Xia; Yaning Chen; Yongyong Zhang; Zhi Li; Shengqing Zhang; Wenyu Wang (Journal of Hydrology, 2023)

Accelerated methane emission from permafrost regions since the 20th century - Guo-zhi Xie; Li-peng Zhang; Cong-ying Li; Wei-dong Sun (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

A complete genus-level phylogeny reveals the Cretaceous biogeographic diversification of the poppy family - Huan-Wen Peng; Kun-Li Xiang; Andrey S. Erst; Lian Lian; Rosa Del C. Ortiz; Florian Jabbour; Zhi-Duan Chen; Wei Wang (Molecular Phylogenetics and Evolution, 2023)

Toward sustainable green alumina production: A critical review on process discharge reduction from gibbsitic bauxite and large-scale applications of red mud - Guo-tao Zhou; Yi-lin Wang; Tian-gui Qi; Qiu-sheng Zhou; Gui-hua Liu; Zhi-hong Peng; Xiao-bin Li (Journal of Environmental Chemical Engineering, 2023)

Exploration of two-stage cultivation strategy using nitrogen limited and phosphorus sufficient to simultaneously improve the biomass and lipid productivity in Desmodesmus intermedius Z8 - Zhi Li; Shuaiying Peng; Qiuling Li; Saijin Wei; Qinghua Zhang; Xuejiao An; Hanguang Li (Fuel, 2023)

Oral vaccination with recombinant Lactobacillus casei with surface displayed OmpK fused to CTB as an adjuvant against Vibrio mimicus infection in Carassius auratus - Hong-Jin Li; Bin-Tong Yang; Yu-Feng Sun; Tong Zhao; Zhi-Peng Hao; Wei Gu; Meng-Xia Sun; Wei Cong; Yuan-Huan Kang (Fish & Shellfish Immunology, 2023)

Arsenic induced plant growth by increasing its nutrient uptake in As-hyperaccumulator Pteris vittata: Comparison of arsenate and arsenite - You-Jing Peng; Chun-Yan Hu; Wei Li; Zhi-Hua Dai; Chen-Jing Liu; Lena Q. Ma (Environmental Pollution, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Daily precipitation and temperature for 2021–2050 over China: Multiple RCMs and emission scenarios corrected by a trend‐preserving method - Jingpeng Zhang; Shouzhang Peng; Zhengshi Wang; Jinxia Fu; Zhi Li (International Journal of Climatology, 2023)
Daily climate data are extremely important to drive ecological models, but the outputs of climate models are often deviated from the observations. The bias correction methods mostly highlight the target statistical parameters (e.g., mean and variance) for a target period, but perturb the simulated change trend and variability. In this study, we utilize a trend‐preserving bias correction method that can simultaneously consider the frequency and intensity of climatic variables to adjust the daily maximum and minimum temperature, and precipitation (Tmax, Tmin, and Pre) from CORDEX‐EA regional climate models for the period of 2021–2050 over China. Results show that: (a) the bias correction method greatly improves the spatial patterns of simulated Tmax, Tmin, and Pre since the corrected data has higher correlation and smaller differences across the whole domain. The differences in mean Tmax, Tmin, and Pre between climate models and observations have been reduced from −4.5 ± 6.41°C, −2.06 ± 0.58°C, 177.25 ± 51.55 mm before correction to 0.01 ± 0.02°C, −0.01 ± 0.02°C, −26.22 ± 6.39 mm after correction, respectively. In addition, the simulated change trend and climate variability at all time scales are well preserved. (b) Spatially, the warming rates in the west would be higher than in the east, and they are larger under the most severe future emissions scenario (RCP8.5) relative to the low‐mid emissions scenario (RCP4.5). The Pre change would mainly occur over east China with the significant upward trend. The dataset presented in this article has been published in the Network Common Data Form (NetCDF) File Format at https://doi.org/10.5281/zenodo.5058620 .

Air pollution in heavy industrial cities along the northern slope of the Tianshan Mountains, Xinjiang: characteristics, meteorological influence, and sources - Yutian Luo; Liping Xu; Zhongqin Li; Xi Zhou; Xin Zhang; Fanglong Wang; Jiajia Peng; Cui Cao; Zhi Chen; Heng Yu (Environmental Science and Pollution Research, 2023)

Identifying the fundamental drives behind the 10-year evolution of northern China's rural household energy and emission: Implications for 2030 and beyond - Yuzhe Zhang; Guorui Zhi; Wenjing Jin; Peng Xu; Zhengying Li; Yao Kong; Haitao Zhang; Yi Shen; Jingnan Hu (Science of The Total Environment, 2023)

Enhanced degradation of poly(ethylene terephthalate) by the addition of lactic acid / glycolic acid: composting degradation, seawater degradation behavior and comparison of degradation mechanism - Tian-Yuan Liu; Peng-Yuan Xu; Dan Huang; Bo Lu; Zhi-Chao Zhen; Wei-Zhen Zheng; Yan-Chao Dong; Xiao Li; Ge-Xia Wang; Jun-Hui Ji (Journal of Hazardous Materials, 2023)

Numerical and experimental investigations of concrete lined compressed air energy storage system - Peng Li; Huan Kang; Qing Zhu; Yang Wu; Jing Zhang; Liyang Fan; Zhi Wang (Journal of Cleaner Production, 2023)

Insights into the interaction mechanism of glutelin and rice starch during extrusion processing: The role of specific mechanical energy - Li-shuang Wang; Yu-min Duan; Li-feng Tong; Xiao-shuai Yu; Zhi-gang Xiao; Peng Wang (Food Chemistry, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

A highly sensitive electrochemical immunosensor based on electrospun nanocomposite for the detection of parathion - Wen-jia Yin; Jing-xian Zhang; Hong Wang; Yu Wang; Xi Zeng; Zhen-lin Xu; Jin-yi Yang; Zhi-li Xiao; Bruce D. Hammock; Peng Wen (Food Chemistry, 2023)

Construction and validation of a bladder cancer risk model based on autophagy-related genes - Chong Shen; Yan Yan; Shaobo Yang; Zejin Wang; Zhouliang Wu; Zhi Li; Zhe Zhang; Yuda Lin; Peng Li; Hailong Hu (Functional & Integrative Genomics, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Antibiotics disrupt lipid metabolism in zebrafish (Danio rerio) larvae and 3T3-L1 preadipocytes - Yuyang Lei; Fangfang Li; Monika Mortimer; Zhi Li; Bi-Xia Peng; Minjie Li; Liang-Hong Guo; Guoqiang Zhuang (Science of The Total Environment, 2023)

Three new chemical constituents from the roots of Schisandra chinensis and their neuroprotective effects - Yan Liu; Yan-Ying Li; Yuan Liu; Zi-Qi Peng; Si-Yi Wang; Yi-Kai Jiang; Juan Pan; Wei Guan; Zhi-Chao Hao; Anam Naseem; Hai-Xue Kuang; Bing-You Yang (Phytochemistry Letters, 2023)

NOx emission prediction using a lightweight convolutional neural network for cleaner production in a down-fired boiler - Zhi Wang; Xianyong Peng; Shengxian Cao; Huaichun Zhou; Siyuan Fan; Kuangyu Li; Wenbo Huang (Journal of Cleaner Production, 2023)

A demonstration concentrating solar power plant in China: Carbon neutrality, energy renewability and policy perspectives - Huafeng Ye; Huaiwu Peng; Chaohui Li; Yilin Li; Zhi Li; Qing Yang; Guoqian Chen (Journal of Environmental Management, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

Recent updates on targeting the molecular mediators of NAFLD - Jia Wang; Lei Wang; Xiao-Jing Zhang; Peng Zhang; Jingjing Cai; Zhi-Gang She; Hongliang Li (Journal of Molecular Medicine, 2023)

Improving atmospheric particulate matter removal of residential green space based on Landscape patterns and plant functional types - Zhi Zhang; Yu Li; Muni Li; Huan Meng; Tong Zhang; Zequn Peng; Weikang Zhang (Air Quality, Atmosphere & Health, 2023)

Episodic ventilation of euxinic bottom waters triggers the formation of black shale-hosted Mn carbonate deposits - Zhi-Guo Dong; Zi-Dong Peng; Leslie J. Robbins; Kurt O. Konhauser; Bang-Lu Zhang; Lian-Chang Zhang; Jie Li; Wen-Jun Li; Le Zhang; Chang-Le Wang (Geochimica et Cosmochimica Acta, 2023)

Two-birds-one-stone: Flexible PANI film with bionic microstructures for multifunctional sensing of physical and chemical stimuli - Li Xu; Chong Liu; Xu Ma; Yuqing Xu; Wei Zhou; Wei Guan; Qinping Qiang; Tianchun Lang; Lingling Peng; Yang Zhong; Yakovlev Alexey Nikolaevich; Zhi Zhou; et al. (Chemical Engineering Journal, 2023)

Transcriptional analysis of heavy metal P1B-ATPases (HMAs) elucidates competitive interaction in metal transport between cadmium and mineral elements in rice plants - Peng Tian; Yu-Xi Feng; Cheng-Zhi Li; Ping Zhang; Xiao-Zhang Yu (Environmental Science and Pollution Research, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Identification of a stable major-effect quantitative trait locus for pre-harvest sprouting in common wheat (Triticum aestivum L.) via high-density SNP-based genotyping - Zhi Li; Yongyan Chen; Xia Ou; Mengning Wang; Nanxin Wang; Wei Li; Yawen Deng; Yixin Diao; Zixin Sun; Qinyi Luo; Xinli Li; Liqi Zhao; et al. (Theoretical and Applied Genetics, 2022)

Causal gene identification and desirable trait recreation in goldfish - Peng Yu; Yang Wang; Zhi Li; Hui Jin; Liang-Liang Li; Xiao Han; Zhong-Wei Wang; Xiao-Li Yang; Xi-Yin Li; Xiao-Juan Zhang; Li Zhou; Jian-Fang Gui (Science China Life Sciences, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Genetic variations in the bitter taste receptor gene TAS2R38 are related to cigarette smoking behavior in Han Chinese smokers - Fei-Yan Qi; Zhou-Hai Zhu; Meng Li; Ying Guan; Qi-Yuan Peng; She-Ming Lu; Zhi-Hua Liu; Ming-Feng Wang; Ming-Ming Miao; Zhang-Yu Chen; Xue-Mei Li; Jie Bai; et al. (Genes & Genomics, 2022)

Response of the metabolic and autophagy pathways in Mytilus under starvation - Bing Xie; Chuan-yue Chen; Xiaolin Zhang; Si-yuan Li; Zhong-qi Gu; Ji Huang; Jian-yu He; Peng-zhi Qi; Bao-ying Guo; Zhi Liao; Xiaojun Yan (Frontiers in Marine Science, 2022)
Being an industrially valuable species of bivalve, Mytilus is widespread in the area around the eastern coast of China. Starvation is an environmental stress that mussels often encounter in their growth. However, few report carried out on the physiological and biochemical response and molecular regulation and adaptation mechanism of mussels under starvation. To illustrate the molecular mechanism of hosts of Mytilus to starvation, the gill transcriptome was used for analysis before and after 9 days of starvation in Mytilus using the Illumina/HiSeq-2000 deep sequencing platform, accompanied by the study of differentially expressed genes (DEGs). In total, 42.137 GB of clean data were obtained from six sample libraries, the average amount of clean data of each sample is 7.023 GB, and 58,540 unigenes that average 780 bp in length were assembled. Unigenes were illustrated by commenting them against the NR, Swiss-Prot, Pfam, String, GO and KEGG databases. After 9 days of starvation, 2,188 and 2,672 genes were determined to be significantly up- or down-regulated expression genes, separately. Amongst, 4,860 genes were associated with 260 pathways, contains vital enrichment pathways, such as “Metabolic”, “PI3K-Akt signaling pathway”, “Phagosome”, “Apoptosis” and “Lysosome”. In inclusion, autophagy cells were investigated by an electron microscopy, alongside further observations of the expression of autophagy-related genes in gill tissue before and after starvation. The data indicates that the amount of autophagosomes increased and found that atg2 , atg6 and atg13 were significantly up-regulated. These results indicated that Mytilus may use autophagy to cope with their damage after starvation. With our research results, we have contributed to a deeper understanding of the role of the molecular mechanisms of immune defence in Mytilus under environmental stress, which has given insights into mussel breeding and the understanding of the molecular mechanisms of Mytilus immune system.

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

An update on microneedle-based systems for diabetes - Wen Xuan Li; Xiao Peng Zhang; Bo Zhi Chen; Wen Min Fei; Yong Cui; Can Yang Zhang; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

Spatiotemporally varied extreme precipitation events simultaneously controlled by multiple circulation factors in China's Loess Plateau - Yuling Ren; Jingpeng Zhang; Jinxia Fu; Shouzhang Peng; Zhi Li (International Journal of Climatology, 2022)
The intensive and frequent extreme precipitation events (EPE) greatly contribute to the severe soil loss in China's Loess Plateau, and it is thus essential to understand how and why EPE varies with space and time. Particularly, the combined influence of multiple factors on EPE has rarely been explored. This study analysed the spatiotemporal variability of EPE for 1961–2017 after defining six indices for intensity, frequency, and duration of EPE (R5d, SDII, R90t, R90n, CDD, CWD). We employed 12 atmospheric circulation factors to determine their combined effects on EPE on different time scales over time by the multiple wavelet coherence. The EPE indices spatially varied with obvious southeast‐northwest gradients. Averaged across the whole plateau, SDII, R90t, and R90n increased insignificantly, while R5d, CDD, and CWD decreased insignificantly. In addition, the change trend had spatial variations with most wet EPE indices increasing in the north and the southernmost areas and decreasing in the middle‐south areas. SDII, R90t, and R90n at 68%, 66%, and 53% of stations tended to increase, respectively, and R5d, CDD, and CWD decreased at 66%, 70%, and 77% of stations, respectively. The temperature had a greater correlation with the duration of EPE in summer and on the intensity and frequency of EPE in winter. El Niño‐Southern Oscillation (ENSO), Pacific North American teleconnection pattern (PNA), ENSO‐Arctic Oscillation (AO), and ENSO‐AO‐PNA were found to be the main factors influencing EPE individually or simultaneously. This study provides technical support for the identification of combined effects of multiple factors, and the results are helpful for regional environmental management. Specific to the Loess Plateau, the identified individual or multiple factors can be used to project future changes in EPE, and the more frequent and intensive EPE in some regions may increase the difficulty in future soil loss control.

Two new clerodane diterpenoids and a new pyran-2-one derivative with anti-neuroinflammatory activities from Croton crassifolius - Zhi-Peng Ling; Qing Tang; Can-Jie Li; Jin-Lin Tan; Hai-Yue Zhao; Yi-Kun Hao; Zhao-Chun Zhan; Zhong-Nan Wu; Yu-Bo Zhang; Qing Zheng; Guo-Cai Wang (Journal of Natural Medicines, 2022)

Comparative transcriptome analysis of the differentiating gonads in Scatophagus argus - Umar Farouk Mustapha; You-Xing Peng; Yuan-Qing Huang; Daniel Assan; Fei Zhi; Gang Shi; Yang Huang; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2022)
The reproductive-related studies, including genetic and genomic such as gonadal transcriptome analyses, have previously focused on the adult spotted scat, with little information on juvenile fish. Transcriptomics is a powerful tool that allows for massive parallel analysis to identify differential expression and the patterns of gene expression holistically at a particular stage in a cell or tissue development. This study presents the first report on gonadal transcriptome analysis of the differentiating (juvenile; 4 months after hatch; stage I ovary and testis) spotted scat gonads. The study revealed potential reproduction and gonadal development-related genes. A total of 25936 genes were identified, of which 16248 were co-expressed, 17893 and 17258 expressed in males and females, respectively, from sequence data of testis I (n = 3) and ovary I (n = 2). A total of 6549 differentially expressed genes (DEGs) were identified between males and females. Genes attributable to male gonad development pathway such as dmrt1 , gsdf , and amh are significantly expressed in differentiating testes, while female-related genes such as foxl2, cyp19a1a, 42sp50 and sox3 were expressed considerably in differentiating ovaries. In addition, dmrt1/dmrt1y was not expressed in the female (FPKM=0.00), while its paralog dmrt1b was expressed in both males and females. In the male pathway, dmrt1y and gsdf are critical for sex determination and maintenance while foxl2/foxl3 and cyp19a1a are critical in the female development pathway. The current studies provide an insight into the expression patterns of sex and gonadal-related genes in differentiating gonads of spotted scat.

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Influence of particle breakage on the isotropic compressibility of sands - Fang-wei Yu; Li-jun Su; Xiong-zhi Peng (Journal of Mountain Science, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

The effect of meteorological drought on vegetation cover in the Yellow River basin, China - Lu Jia; Kun‐xia Yu; Zhan‐bin Li; Peng Li; Guo‐ce Xu; Yu‐ting Cheng; Xiang Zhang; Zhi Yang (International Journal of Climatology, 2022)
As a widespread natural disaster, drought has a significant impact on changes in regional vegetation cover. Based on 1‐month standardized precipitation index (SPI1), this study took the Yellow River basin (YRB) with frequent droughts as the research object, using NDVI data from 1999 to 2018, Mann–Kendall trend test, and correlation test to study the temporal and spatial characteristics of meteorological drought, explored the response of vegetation cover to meteorological drought, and further discussed the possible factors affecting meteorological drought. The results of the study showed that from 1999 to 2018, the SPI1 in the YRB had not increased significantly in a large area in different months ( p > .05). On the monthly time scale, the NDVI of the YRB gradually increased from north to south, showing a significant increasing trend the central area ( p p p

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Understanding the Sources of Heavy Metal Pollution in Ambient Air of Neighboring a Solid Waste Landfill Site - Umangi H. Mehta; Daya S. Kaul; Dane Westerdahl; Zhi Ning; Kai Zhang; Li Sun; Peng Wei; Hardik H. Gajjar; Jai D. Jeyaraman; Mansi V. Patel; Rutu R. Joshi (Aerosol Science and Engineering, 2022)

Environmental drivers of soil microbial activity and diversity along an elevational gradient - Si-li Peng; Zhi-wei Ge; Gang-cai Liu; Ling-feng Mao (Journal of Mountain Science, 2022)

Identification and validation of quantitative trait loci for the functional stay green trait in common wheat (Triticum aestivum L.) via high-density SNP-based genotyping - Tianheng Ren; Tao Fan; Shulin Chen; Yongyan Chen; Xia Ou; Qing Jiang; Wanhua Peng; Zhenglong Ren; Feiquan Tan; Peigao Luo; Zhi Li (Theoretical and Applied Genetics, 2022)

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Discerning the Putative U and V Chromosomes of Saccharina japonica (Phaeophyta) by Cytogenetic Mapping of Sex-Linked Molecular Markers - Yu Du; Peng-Fei Liu; Zhi Li; Qian Zheng; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2022)
Saccharina japonica , an importantly industrial species in brown seaweeds, has a typical alternate life history of heteromorphic generations and UV sex determination system. But up to now, the sex chromosomes, U and V, in this kelp remain to be evidenced cytologically. In the present study, the female-linked (SJ-f_000170 and MSj68-58-2) and male-linked (SJ-13_001840 and MSj68-16-2) molecular markers developed on the basis of Ectocarpus sex-determining regions (SDRs) were selected after PCR amplification and Southern blotting analysis. Mono-color fluorescence in situ hybridization (FISH) to the kelp metaphase chromosomes with each of these confirmed sex-linked markers as a probe indicated that the hybridization signals were confined to either female or male gametophytes exclusively. The shape and size of hybridized chromosomes and the relative location of these sex-linked markers on them suggested that the marked chromosomes in a sex were the same, which was further confirmed by dual-color FISH observations. SJ-f_000170 and SJ-13_001840, corresponding to each sex, were therefore used to map the sporophyte metaphase chromosomes by dual-color FISH technique, and they were hybridized on different chromosomes as expected. The sporophyte metaphase chromosomes as hybridized by SJ-f_000170 and SJ-13_001840 resembled those in either female or male gametophytes, suggesting that they were the putative U and V, respectively, chromosomes in S . japonica . To further demonstrate the reliability of this inference, genomic information of the screened bacterial artificial chromosome (BAC) clones carrying two female-linked markers, for example, from the constructed BAC libraries of the kelp female gametophytes was provided. The insert sequencing of two selected BAC clones revealed that repetitive elements were rich whereas gene density was poor, which was characterized as non-recombining SDR sequences in brown seaweed Ectocarpus sp. and liverwort Marchantia polymorpha . The present study laid a solid foundation for unveiling the mystery of S . japonica sex chromosomes.

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Dissolving microneedle rollers for rapid transdermal drug delivery - Xiao Peng Zhang; Bao Li Zhang; Bo Zhi Chen; Ze Qiang Zhao; Wen Min Fei; Yong Cui; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

Responses and feedback of litter properties and soil mesofauna to herbaceous plants expansion into the alpine tundra on Changbai Mountain, China - Ying-jie Zhang; Ying-hua Jin; Jia-wei Xu; Hong-shi He; Yan Tao; Zhi-peng Yang; Jing Zhao; Yin-xia Diao; Chen-hui Sun; Mai-He Li (Journal of Mountain Science, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Integrative testing device for investigating the hydro-mechanical behavior of highly expansive clay - Yun-zhi Tan; Fan Peng; Hui Li; Hua-jun Ming; De-an Sun (Arabian Journal of Geosciences, 2022)

Alkaloids with acetylcholinesterase inhibitory activity from Corydalis racemosa (Thunb.) Pers - Hui-Na Yao; Zhi-Tian Peng; Yun-Feng Zhang; Di-Fa Liu; Bing-Feng Huang; Peng-Fei Tu; Yun-Fang Zhao; Hui-Xia Huo; Jun Li (Natural Product Research, 2021)

Phenotypic and genomic adaptations to the extremely high elevation in plateau zokor ( Myospalax baileyi ) - Tao Zhang; Jie Chen; Jia Zhang; Yuan‐Ting Guo; Xin Zhou; Meng‐Wen Li; Zhi‐Zhong Zheng; Tong‐Zuo Zhang; Robert W. Murphy; Eviatar Nevo; Peng Shi (Molecular Ecology, 2021)
The evolutionary outcomes of high elevation adaptation have been extensively described. However, whether widely distributed high elevation endemic animals adopt uniform mechanisms during adaptation to different elevational environments remains unknown, especially with respect to extreme high elevation environments. To explore this, we analysed the phenotypic and genomic data of seven populations of plateau zokor ( Myospalax baileyi ) along elevations ranging from 2,700 to 4,300 m. Based on whole‐genome sequencing data and demographic reconstruction of the evolutionary history, we show that two populations of plateau zokor living at elevations exceeding 3,700 m diverged from other populations nearly 10,000 years ago. Further, phenotypic comparisons reveal stress‐dependent adaptation, as two populations living at elevations exceeding 3,700 m have elevated ratios of heart mass to body mass relative to other populations, and the highest population (4,300 m) displays alterations in erythrocytes. Correspondingly, genomic analysis of selective sweeps indicates that positive selection might contribute to the observed phenotypic alterations in these two extremely high elevation populations, with the adaptive cardiovascular phenotypes of both populations possibly evolving under the functional constrains of their common ancestral population. Taken together, phenotypic and genomic evidence demonstrates that heterogeneous stressors impact adaptations to extreme elevations and reveals stress‐dependent and genetically constrained adaptation to hypoxia, collectively providing new insights into the high elevation adaptation.

Influence of grain segregation on the behavior of sand in triaxial tests - Fang-wei Yu; Xiong-zhi Peng; Li-jun Su (Journal of Mountain Science, 2021)

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora - Yun Liu; Jian‐Fei Ye; Hai‐Hua Hu; Dan‐Xiao Peng; Li‐Na Zhao; Li‐Min Lu; Wajid Zaman; Zhi‐Duan Chen (Journal of Biogeography, 2021)
Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya and adjacent areas and reconstructed a species‐level phylogenetic tree of 19,313 angiosperm species. The area was divided into 398 grid cells, each 1 × 1°. Nine datasets of different elevation ranges were then used to delineate the flora of the Sino‐Himalaya and adjacent areas using the phylogenetic dissimilarity approach. Results A comparison of nine regionalisation schemes of the Sino‐Himalayan flora based on different elevation range datasets revealed that more than half of grid cells were allocated to more than one subregion. Most of these grid cells were located in areas with a wide range of elevation and/or at the boundaries between subregions. After revising the subregion allocations of eight shifting grid cells, we generated a phylogeny‐ and elevation‐based regionalisation scheme of three regions, comprising eight subregions, for the Sino‐Himalayan flora. Main conclusions By integrating phylogenetic and elevational information, the Sino‐Himalaya can be divided into three floristic regions: the Yunnan Plateau region, the Hengduan Mountains region and the East Himalaya region. Our study provides novel insights into the regionalisation of the flora and highlights the importance of incorporating elevation data in the bioregionalisation of areas with a broad elevational range.

Rock physics inversion based on an optimized MCMC method - Jia-Jia Zhang; Hong-Bing Li; Guang-Zhi Zhang; Yi-Peng Gu; Zhuo-Fan Liu (Applied Geophysics, 2021)

Experimental Study of Stirring and Resin-Blocking Devices for Improving the Performance of Resin-Anchored Cable Bolts - Housheng Jia; Yinwei Wang; Shaowei Liu; Lei Wang; Guanghui Zhi; Bo Peng; Yongen Li (Rock Mechanics and Rock Engineering, 2021)

Co-culture: stimulate the metabolic potential and explore the molecular diversity of natural products from microorganisms - Xiao-Yue Peng; Jin-Tao Wu; Chang-Lun Shao; Zhi-Yong Li; Min Chen; Chang-Yun Wang (Marine Life Science & Technology, 2021)

Upregulation of the PPAR signaling pathway and accumulation of lipids are related to the morphological and structural transformation of the dragon-eye goldfish eye - Peng Yu; Yang Wang; Wen-Tao Yang; Zhi Li; Xiao-Juan Zhang; Li Zhou; Jian-Fang Gui (Science China Life Sciences, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Nitrogen fertilizer management affects remobilization of the immobilized cadmium in soil and its accumulation in crop tissues - Jun-Feng Wang; Wan-Li Li; Qu-Sheng Li; Li-Li Wang; Tao He; Fo-Peng Wang; Zhi-Min Xu (Environmental Science and Pollution Research, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Can Swimming Microalgal Cells be Vehicles for ZnO Nanoparticle Transportation and Thus Lead to Zn Diffusion? - Shuai Mao; Hongxia Liu; Jiji Li; Yahong Guo; Wei Ma; Peng zhi Qi; Chengkai Qu (Bulletin of Environmental Contamination and Toxicology, 2021)

Investigating nanoparticle formation and the metabolic response of Ulva prolifera to gold ions - Meihua Fan; Zhi Liao; JianXin Wang; Xiaolin Zhang; Peng Li; Mengxiong Yin (Journal of Applied Phycology, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

A new demethyl abietane diterpenoid from the roots of Tripterygium wilfordii - Peng Li; Shao-Xin Shen; Ling-Xue Liu; Jian-Hua Xu; Xin-Hua Ma; Dong-Mei Shi; Zhi-Qiang Zhang (Natural Product Research, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Transcriptome analysis of rice leaves in response to Rhizoctonia solani infection and reveals a novel regulatory mechanism - De Peng Yuan; Xiao Feng Xu; Woo-Jong Hong; Si Ting Wang; Xin Tong Jia; Yang Liu; Shuang Li; Zhi Min Li; Qian Sun; Qiong Mei; Shuai Li; Ki-Hong Jung; et al. (Plant Biotechnology Reports, 2020)

Noise does not equal bias in assessing the evolutionary history of the angiosperm flora of China: A response to Qian (2019) - Li‐Min Lu; Hai‐Hua Hu; Dan‐Xiao Peng; Bing Liu; Jian‐Fei Ye; Tuo Yang; Hong‐Lei Li; Miao Sun; Stephen A. Smith; Pamela S. Soltis; Douglas E. Soltis; Zhi‐Duan Chen (Journal of Biogeography, 2020)
In response to our paper on the evolutionary history of the Chinese flora, Qian suggests that certain features of the divergence time estimation employed might have led to biased conclusions in Lu et al (2018). Here, we consider Qian's specific criticisms, explore the extent of uncertainty in the data and demonstrate that (i) no systematic bias toward dates that are too young or too old is detected in Lu et al.; (ii) constraint of the crown age of angiosperms does not bias the generic ages estimated by Lu et al.; and (iii) ages derived from the Chinese regional phylogeny do not bias the conclusions reported by Lu et al. All these analyses confirm that the conclusions reported previously are robust. We argue that, like many large‐scale biodiversity analyses, sources of noise in divergence time estimation are to be expected, but these should not be confused with bias.

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Water and salt stresses do not trigger bottom-up effects on plant-mediated indirect interactions between a leaf chewer and a sap-feeder - Yong-Cheng Dong; Zhi-Jian Wang; Rong-Yan Bu; Hui-Jie Dai; Li-Jun Zhou; Peng Han; Edwige Amiens-Desneux; Philippe Bearez; Nicolas Desneux (Journal of Pest Science, 2020)

Ectopic expression of an oat SnRK2 gene, AsSnRK2D, enhances dehydration and salinity tolerance in tobacco by modulating the expression of stress-related genes - Dian-Jun Xiang; Li-Li Man; Shuai Cao; Peng Liu; Zhi-Gang Li; Xiao-Dong Wang (Brazilian Journal of Botany, 2020)

Evoked-potential audiogram variability in a group of wild Yangtze finless porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhi-Tao Wang; Jiao Li; Peng-Xiang Duan; Zhi-Gang Mei; Fu-Qiang Niu; Tomonari Akamatsu; Pei-Yu Lei; Lu Zhou; Jing Yuan; Yu-Wei Chen; Alexander Ya Supin; Ding Wang; et al. (Journal of Comparative Physiology A, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

A new diterpenoid alkaloid from Aconitum hemsleyanum - Zhi-Hui Luo; Yang Chen; Xin-Yi Sun; Hua Fan; Wei Li; Liang Deng; Tian-Peng Yin (Natural Product Research, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

The basic helix-loop-helix transcription factor OsBLR1 regulates leaf angle in rice via brassinosteroid signalling - Kun Wang; Meng-qi Li; Yan-peng Chang; Bo Zhang; Quan-zhi Zhao; Wen-li Zhao (Plant Molecular Biology, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

Effects of Dietary Supplementation of Recombinant Plectasin on Growth Performance, Intestinal Health and Innate Immunity Response in Broilers - Jing Lin Ma; Li Hua Zhao; Dan Dan Sun; Jing Zhang; Yong Peng Guo; Zhi Qiang Zhang; Qiu Gang Ma; Cheng Ji; Li Hong Zhao (Probiotics and Antimicrobial Proteins, 2020)

Stable Genome Incorporation of Sperm-derived DNA Fragments in Gynogenetic Clone of Gibel Carp - Fan Chen; Xi-Yin Li; Li Zhou; Peng Yu; Zhong-Wei Wang; Zhi Li; Xiao-Juan Zhang; Yang Wang; Jian-Fang Gui (Marine Biotechnology, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Identification of Shaker K+ channel family members in Rosaceae and a functional exploration of PbrKAT1 - Guodong Chen; Qian Chen; Kaijie Qi; Zhihua Xie; Hao Yin; Peng Wang; Runze Wang; Zhi Huang; Shaoling Zhang; Li Wang; Juyou Wu (Planta, 2019)

Late Holocene mangrove development and response to sea level change in the northwestern South China Sea - Peng Xia; Xianwei Meng; Zhen Li; Pengyao Zhi; Mengwei Zhao; Enkang Wang (Acta Oceanologica Sinica, 2019)

rTMS combined with motor training changed the inter-hemispheric lateralization - Jing-na Jin; Xin Wang; Ying Li; He Wang; Zhi-peng Liu; Tao Yin (Experimental Brain Research, 2019)

Cloning, molecular characterization, and tissue differential expression of connective tissue growth factor (ctgf) of grass carp - Wen-Qian Pan; Jun-Peng Wang; Zhi-Han Tu; Tian Gan; Jing Hu; Jing Wei; Xiang-Jun Leng; Xiao-Qin Li (Fish Physiology and Biochemistry, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Permanent displacement models of earthquake-induced landslides considering near-fault pulse-like ground motions - Ying-bin Zhang; Chen-lin Xiang; Yan-long Chen; Qian-gong Cheng; Li Xiao; Peng-cheng Yu; Zhi-wang Chang (Journal of Mountain Science, 2019)

Bile-ology: from bench to bedside - Li-hua Jin; Zhi-peng Fang; Min-jie Fan; Wen-dong Huang (Journal of Zhejiang University-SCIENCE B, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Ethyl lucidenates A reverses P-glycoprotein mediated vincristine resistance in K562/A02 cells - Peng Li; Shi-yu Chen; Shao-xin Shen; Ling-xue Liu; Jian-hua Xu; Zhi-qiang Zhang (Natural Product Research, 2019)

Molecular characterization and expression profiles of two insulin-like growth factor 1 receptors during fasting and re-feeding in Siniperca chuatsi - Xiaoli Chen; Gongpei Wang; Xue Lu; Peng Xu; Shuang Zeng; Zhi Chen; Qiaoying Zhu; Guifeng Li (Fisheries Science, 2019)

Influence of rock fractures on the amplitude of dipole-source reflected shear wave - Hao Wang; Ning Li; Cai-Zhi Wang; Hong-Liang Wu; Peng Liu; Yu-Sheng Li; Ying-Ming Liu; Ye Yuan (Applied Geophysics, 2019)

Two new polyketides from the fungus Penicillium oxalicum MHZ153 - Yi Ren; Ling-Hui Chao; Jing Sun; Xiao-Nan Chen; Hui-Na Yao; Zhi-Xiang Zhu; Dan Dong; Ting Liu; Peng-Fei Tu; Jun Li (Natural Product Research, 2019)

Irinotecan Alters the Disposition of Morphine Via Inhibition of Organic Cation Transporter 1 (OCT1) and 2 (OCT2) - Peng Zhu; Zhi Ye; Dong Guo; Zongping Xiong; Shiqiong Huang; Jun Guo; Wei Zhang; James E. Polli; Honghao Zhou; Qing Li; Yan Shu (Pharmaceutical Research, 2018)

Contourlet-based hippocampal magnetic resonance imaging texture features for multivariant classification and prediction of Alzheimer’s disease - Ni Gao; Li-Xin Tao; Jian Huang; Feng Zhang; Xia Li; Finbarr O’Sullivan; Si-Peng Chen; Si-Jia Tian; Gehendra Mahara; Yan-Xia Luo; Qi Gao; Xiang-Tong Liu; et al. (Metabolic Brain Disease, 2018)

Evaluating the suitability of different terrains for sustaining human settlements according to the local elevation range in China using the ASTER GDEM - Chi-wei Xiao; Zhi-ming Feng; Peng Li; Zhen You; Jia-kun Teng (Journal of Mountain Science, 2018)

NaCl promotes antibiotic resistance by reducing redox states in Vibrio alginolyticus - Jun Yang; Zao‐Hai Zeng; Man‐Jun Yang; Zhi‐Xue Cheng; Xuan‐Xian Peng; Hui Li (Environmental Microbiology, 2018)
Summary The development of antibiotic resistance in Vibrio alginolyticus represents a threat to human health and fish farming. Environmental NaCl regulation of bacterial physiology is well documented, but whether the regulation contributes to antibiotic resistance remains unknown. To explore this, we compared minimum inhibitory concentration (MIC) of V. alginolyticus cultured in different media with 0.5%–10% NaCl, and found that the MIC increased as the NaCl concentration increased, especially for aminoglycoside antibiotics. Consistent with this finding, internal NaCl also increased, while intracellular gentamicin level decreased. GC–MS‐based metabolomics showed different distributions of pyruvate cycle intermediates among 0.5%, 4% and 10% NaCl. Differential activity of enzymes in the pyruvate cycle and altered expression of Na(+)‐NQR led to a reducing redox state, characterized by decreased levels of NADH, proton motive force (PMF) and ATP. Meanwhile, NaCl negatively regulated PMF as a consequence of the reducing redox state. These together are responsible for the decreased intracellular gentamicin level with the increased external level of NaCl. Our study reveals a previously unknown redox state‐dependent mechanism regulated by NaCl in V. alginolyticus that impacts antibiotic resistance.

Identification of Auxin Activity Like 1, a chemical with weak functions in auxin signaling pathway - Wenbo Li; Haimin Li; Peng Xu; Zhi Xie; Yajin Ye; Lingting Li; Deqiang Li; Yijing Zhang; Laigeng Li; Yang Zhao (Plant Molecular Biology, 2018)

Hydrological response of biological soil crusts to global warming: A ten‐year simulative study - Xin‐Rong Li; Rong‐Liang Jia; Zhi‐Shan Zhang; Peng Zhang; Rong Hui (Global Change Biology, 2018)
Biological soil crusts across the desert regions play a key role in regional ecological security and ecological health. They are vital biotic components of desert ecosystems that maintain soil stability, fix carbon and nitrogen, influence the establishment of vascular plants, and serve as habitats for a large number of arthropods and microorganisms, as well as influencing soil hydrological processes. Changes in temperature and precipitation are expected to influence the functioning of desert ecosystems by altering biotic components such as the species composition of biological soil crusts. However, it remains unclear how these important components will respond to the prolonged warming and reduced precipitation that is predicted to occur with climate change. To evaluate how the hydrological properties of these biological soil crusts respond to these alterations, we used open‐top chambers over a 10‐year period to simulate warming and reduced precipitation. Infiltration, dew entrapment, and evaporation were measured as surrogates of the hydrological functioning of biological soil crusts. It was found that the ongoing warming coupled with reduced precipitation will more strongly affect moss in crustal communities than lichens and cyanobacteria, which will lead to a direct alteration of the hydrological performance of biological soil crusts. Reductions in moss abundance, surface cover, and biomass resulted in a change in structure and function of crustal communities, decreased dew entrapment, and increased infiltration and evaporation of biological soil crusts in desert ecosystems, which further impacted on the desert soil water balance.

Novel alternatively spliced isoforms of MEF2A and their mRNA expression patterns in pigs - Xiao Hong Guo; Qi Zhang; Meng Li; Peng Fei Gao; Guo Qing Cao; Zhi Min Cheng; Ning Fang Zhang; Bao Yu Le; Jian Feng Liu; Xiao Jun Liu; Bu Gao Li (Journal of Genetics, 2018)

Forward modeling of ocean-bottom cable data and wave-mode separation in fluid–solid elastic media with irregular seabed - Ying-Ming Qu; Jun-Zhi Sun; Zhen-Chun Li; Jian-Ping Huang; Hai-Peng Li; Wen-Zhi Sun (Applied Geophysics, 2018)

Stable expression of infliximab in CRISPR/Cas9-mediated BAK1-deficient CHO cells - Zhi Miao; Qian Li; Jian Zhao; Peng Wang; Lei Wang; Hong-Peng He; Nan Wang; Hao Zhou; Tong-Cun Zhang; Xue-Gang Luo (Biotechnology Letters, 2018)

Re-delineating mountainous areas with three topographic parameters in Mainland Southeast Asia using ASTER global digital elevation model data - Chi-wei Xiao; Peng Li; Zhi-ming Feng (Journal of Mountain Science, 2018)

Response of the wheat rhizosphere soil nematode community in wheat/walnut intercropping system in Xinjiang, Northwest China - Peng-hua Bai; Qi-Zhi Liu; Xing-yue Li; Yan-bin Liu; Lin-lin Zhang (Applied Entomology and Zoology, 2018)

An improved grey wolf optimizer algorithm for the inversion of geoelectrical data - Si-Yu Li; Shu-Ming Wang; Peng-Fei Wang; Xiao-Lu Su; Xin-Song Zhang; Zhi-Hui Dong (Acta Geophysica, 2018)

A new Em-like protein from Lactuca sativa, LsEm1, enhances drought and salt stress tolerance in Escherichia coli and rice - Dian-Jun Xiang; Li-Li Man; Chun-Lan Zhang; Peng-Liu; Zhi-Gang Li; Gen-Chang Zheng (Protoplasma, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Cloning, purification and biochemical characterisation of a GH35 beta-1,3/beta-1,6-galactosidase from the mucin-degrading gut bacterium Akkermansia muciniphila - Bi-Shan Guo; Feng Zheng; Lucy Crouch; Zhi-Peng Cai; Meng Wang; David N. Bolam; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

A Semi-analytical Model for Pressure-Dependent Permeability of Tight Sandstone Reservoirs - Su-Yang Zhu; Zhi-Min Du; Chuan-Liang Li; Alireza Salmachi; Xiao-Long Peng; Chao-Wen Wang; Ping Yue; Peng Deng (Transport in Porous Media, 2018)

Sources and transformations of nitrogen in the South China Sea: insights from nitrogen isotopes - Zhi Yang; Jianfang Chen; Min Chen; Lihua Ran; Hongliang Li; Peng Lin; Yong Zhu; Chunsheng Wang; Zhongqiang Ji; Jingjing Zhang (Journal of Oceanography, 2018)

Indinavir Alters the Pharmacokinetics of Lamivudine Partially via Inhibition of Multidrug and Toxin Extrusion Protein 1 (MATE1) - Qing Li; Zhi Ye; Peng Zhu; Dong Guo; Hong Yang; Jin Huang; Wei Zhang; James E. Polli; Yan Shu (Pharmaceutical Research, 2018)

RETRACTED ARTICLE: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2018)

Biotoxicity of Cry1Ab protein on wolf spider Pardosa pseudoannulata - Juan Wang; Yuande Peng; Huilin Yang; Zhenzhen Yan; Qinjin Li; Yixue Shi; Chunliang Xie; Yunshan Liang; Zhi Wang; Qisheng Song (Ecotoxicology, 2017)

Black-and-white snub-nosed monkey (Rhinopithecus bieti) feeding behavior in a degraded forest fragment: clues to a stressed population - Zhi-Pang Huang; Matthew B. Scott; Yan-Peng Li; Guo-Peng Ren; Zuo-Fu Xiang; Liang-Wei Cui; Wen Xiao (Primates, 2017)

Synthesis and antiproliferative properties of novel naringenin derivatives - Su-You Liu; Jiang Zeng; Kun-Jian Peng; Li-Chao Zhang; Li-Jun Liu; Zhi-Yong Luo; Da-You Ma (Medicinal Chemistry Research, 2017)

A back-propagation neural-network-based displacement back analysis for the identification of the geomechanical parameters of the Yonglang landslide in China - Fang-wei Yu; Xiong-zhi Peng; Li-jun Su (Journal of Mountain Science, 2017)

Shear wave velocity prediction during CO2-EOR and sequestration in the Gao89 well block of the Shengli Oilfield - Lin Li; Jin-Feng Ma; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu (Applied Geophysics, 2017)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Optimized monitoring sites for detection of biodiversity trends in China - Haigen Xu; Mingchang Cao; Yi Wu; Lei Cai; Yun Cao; Hui Ding; Peng Cui; Jun Wu; Zhi Wang; Zhifang Le; Xiaoqiang Lu; Li Liu; et al. (Biodiversity and Conservation, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Genetic diagnosis of a Chinese multiple endocrine neoplasia type 2A family through whole genome sequencing - Zhen-Fang Du; Peng-Fei Li; Jian-Qiang Zhao; Zhi-Lie Cao; Feng Li; Ju-Ming Ma; Xiao-Ping Qi (Journal of Biosciences, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Solanerioside A, an unusual 14,15-dinor-cyclophytane glucoside from the leaves of Solanum erianthum - Shi-yi Peng; Hang Li; De-po Yang; Bai Bai; Long-ping Zhu; Qin Liu; Juan Shen; Zhi-min Zhao (Natural Product Research, 2017)

Elevated Serum and Cerebrospinal Fluid Free Fatty Acid Levels Are Associated with Unfavorable Functional Outcome in Subjects with Acute Ischemic Stroke - Xiao-Xia Duan; Guan-Peng Zhang; Xiao-Bin Wang; Hua Yu; Jia-Li Wu; Ke-Zhi Liu; Lin Wang; Xiang Long (Molecular Neurobiology, 2017)

Anti-neuroinflammatory constituents from the fungus Penicillium purpurogenum MHZ 111 - Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Yi Ren; Dan Dong; Jiao Zheng; Ting Liu; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Phosphate and ammonium adsorption of the modified biochar based on Phragmites australis after phytoremediation - Yu-Peng Gong; Zhi-Yi Ni; Zhao-Zhao Xiong; Li-Hua Cheng; Xin-Hua Xu (Environmental Science and Pollution Research, 2017)

Transcriptomic analysis of Casuarina equisetifolia L. in responses to cold stress - Hai-Bo Li; Nan Li; Shao-Zong Yang; Hua-Zheng Peng; Li-Ling Wang; Yong Wang; Xiao-Mian Zhang; Zhi-Hui Gao (Tree Genetics & Genomes, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Overexpression of Tau Rescues Nogo-66-Induced Neurite Outgrowth Inhibition In Vitro - Yu-Chao Zuo; Hong-Lian Li; Nan-Xiang Xiong; Jian-Ying Shen; Yi-Zhi Huang; Peng Fu; Hong-Yang Zhao (Neuroscience Bulletin, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Linking microbial C:N:P stoichiometry to microbial community and abiotic factors along a 3500‐km grassland transect on the Tibetan Plateau - Yong‐Liang Chen; Lei‐Yi Chen; Yun‐Feng Peng; Jin‐Zhi Ding; Fei Li; Gui‐Biao Yang; Dan Kou; Li Liu; Kai Fang; Bei‐Bei Zhang; Jun Wang; Yuan‐He Yang (Global Ecology and Biogeography, 2016)
Aim To explore large‐scale patterns and the drivers of carbon:nitrogen:phosphorus (C:N:P) stoichiometry in heterotrophic microbes. Location A 3500‐km grassland transect on the Tibetan Plateau. Methods We investigated large‐scale C:N:P stoichiometry patterns in the soil microbial biomass and their relationships with abiotic factors and soil microbial community structures by obtaining soil samples from 173 sites across the Tibetan alpine grasslands. Results C:N:P ratios in the soil microbial biomass varied widely among grassland types, with higher microbial C:N, C:P and N:P ratios in the alpine steppe than the alpine meadow. The soil microbial C:N:P ratio (81:6:1) in the alpine steppe was significantly wider than the global average (42:6:1). Combined stepwise regression and generalized additive models revealed that variations in the microbial C:N ratio were primarily related to abiotic variables, with the microbial C:N ratio exhibiting a decreasing trend along the precipitation gradient. In contrast, variations in microbial C:P and N:P ratios were primarily associated with shifts in the community structure of soil microbes. The microbial C:P and N:P ratios were both negatively associated with all components of the soil microbial communities. However, the fungi to bacteria ratio only regulated the microbial C:P ratio. Main conclusions These results demonstrate that microbial C:N:P stoichiometry exhibits significant flexibility across various ecosystem types. This flexibility is partly induced by shifts in microbial community structure and variations in environmental conditions.

Thermal state of soils in the active layer and underlain permafrost at the kilometer post 304 site along the China-Russia Crude Oil Pipeline - Yong-ping Wang; Guo-yu Li; Hui-jun Jin; Lan-zhi Lu; Rui-xia He; Peng Zhang (Journal of Mountain Science, 2016)

Soil organic carbon contents, aggregate stability, and humic acid composition in different alpine grasslands in Qinghai-Tibet Plateau - Zhi-yuan Cao; Yong Wang; Jie Li; Jin-jing Zhang; Nian-peng He (Journal of Mountain Science, 2016)

Runx2 acts downstream of C/EBPβ to regulate the differentiation of uterine stromal cells in mice - Chuan-Hui Guo; Zhan-Peng Yue; Zhi-Kun Bai; Dang-Dang Li; Zhan-Qing Yang; Bin Guo (Cell and Tissue Research, 2016)

Patterns and drivers of soil microbial communities in Tibetan alpine and global terrestrial ecosystems - Yong‐Liang Chen; Jin‐Zhi Ding; Yun‐Feng Peng; Fei Li; Gui‐Biao Yang; Li Liu; Shu‐Qi Qin; Kai Fang; Yuan‐He Yang (Journal of Biogeography, 2016)
Aim Soil microorganisms play key roles in regulating many important ecosystem processes. However, our understanding of the patterns and drivers of soil microbial communities remains limited. This study aims to test the hypothesis that edaphic factors are more important in explaining variations in soil microbial communities than climatic and biotic factors, as soils directly provide substrates and environment for soil microbial communities. Location Tibetan alpine grasslands and global terrestrial biomes. Methods On the basis of phospholipid fatty acid ( PLFA ) analysis, we investigated large‐scale patterns and drivers of soil microbial communities using data obtained from 196 sites within two major grassland types (alpine steppe and alpine meadow) on the Tibetan Plateau. We also explored global patterns of soil microbial communities by analysing published data from around the world. Results Soil microbial PLFA s in Tibetan alpine grasslands were positively associated with mean annual temperature and mean annual precipitation ( MAP ), contradicting patterns previously observed across global biomes. A combined stepwise regression and variation partitioning analysis revealed that soil microbial community variations in Tibetan alpine grasslands were mainly explained by edaphic factors, such as soil organic carbon, C : N ratio, pH and soil texture, then by biotic factors, such as aboveground biomass and plant species richness, and further by climatic factors, such as MAP . The global analysis confirmed that edaphic factors accounted for a greater portion of the variation in soil microbial communities than did climatic and biotic variables. Main conclusions These results provide strong support for the hypothesis that edaphic factors are the dominant drivers of spatial variations in soil microbial communities across regional and global scales.

3D modeling of geological anomalies based on segmentation of multiattribute fusion - Zhi-Ning Liu; Cheng-Yun Song; Zhi-Yong Li; Han-Peng Cai; Xing-Miao Yao; Guang-Min Hu (Applied Geophysics, 2016)

3D finite-difference modeling algorithm and anomaly features of ZTEM - Tao Wang; Han-Dong Tan; Zhi-Qiang Li; Kun-Peng Wang; Zhi-Ming Hu; Xing-Dong Zhang (Applied Geophysics, 2016)

Erratum to: Abyssicoccus albus gen. nov., sp. nov., a novel member of the family Staphylococcaceae isolated from marine sediment of the Indian Ocean - Zhao Jiang; Chang-Guo Yuan; Min Xiao; Xin-Peng Tian; Inam-Ullah Khan; Chang-Jin Kim; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Abyssicoccus albus gen. nov., sp. nov., a novel member of the family Staphylococcaceae isolated from marine sediment of the Indian Ocean - Zhao Jiang; Chang-Guo Yuan; Min Xiao; Xin-Peng Tian; Inam-Ullah Khan; Chang-Jin Kim; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

Elevated Serum Levels of Neopterin at Admission Predicts Depression After Acute Ischemic Stroke: a 6-Month Follow-Up Study - Chao-Zhi Tang; Yu-Ling Zhang; Wen-Sheng Wang; Wei-Guo Li; Ji-Peng Shi (Molecular Neurobiology, 2016)

Targeting Interleukin-1 beta to Suppress Sympathoexcitation in Hypothalamic Paraventricular Nucleus in Dahl Salt-Sensitive Hypertensive Rats - Jie Qi; Xiu-Fang Zhao; Xiao-Jing Yu; Qiu-Yue Yi; Xiao-Lian Shi; Hong Tan; Xiao-Yan Fan; Hong-Li Gao; Li-Ying Yue; Zhi-Peng Feng; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Application and comparison of coaxial correlation diagram and hydrological model for reconstructing flood series under human disturbance - Peng-nian Huang; Zhi-jia Li; Qiao-ling Li; Ke Zhang; Han-chen Zhang (Journal of Mountain Science, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

Serum Levels of High-sensitivity C-Reactive Protein at Admission Are More Strongly Associated with Poststroke Depression in Acute Ischemic Stroke than Homocysteine Levels - Chao-Zhi Tang; Yu-Ling Zhang; Wen-Sheng Wang; Wei-Guo Li; Ji-Peng Shi (Molecular Neurobiology, 2016)

Influence of the characteristics of fault gouge on the stability of a borehole wall - Sheng Wang; Li-yi Chen; Run-qiu Huang; Zhi-jun Li; Jin-sheng Wu; Chao-peng Yuan (Journal of Mountain Science, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Source identification and apportionment of soil cadmium in cropland of Eastern China: a combined approach of models and geographic information system - Yuyou Zhi; Peng Li; Jiachun Shi; Lingzao Zeng; Laosheng Wu (Journal of Soils and Sediments, 2016)

Location- and Subunit-Specific NMDA Receptors Determine the Developmental Sevoflurane Neurotoxicity Through ERK1/2 Signaling - Wen-Yuan Wang; Li-Jie Jia; Yan Luo; Hong-Hai Zhang; Fang Cai; Hui Mao; Wei-Cai Xu; Jun-Biao Fang; Zhi-You Peng; Zheng-Wen Ma; Yan-Hong Chen; Juan Zhang; et al. (Molecular Neurobiology, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

County-scale temporal–spatial distribution and variability tendency of heavy metals in arable soils influenced by policy adjustment during the last decade: a case study of Changxing, China - Peng Li; Yuyou Zhi; Jiachun Shi; Lingzao Zeng; Laosheng Wu (Environmental Science and Pollution Research, 2015)

Associations of hypoxia inducible factor-1α gene polymorphisms with susceptibility to digestive tract cancers: a case–control study and meta-analysis - Zhi-Hai Ni; Xian-Jun Liang; Jing-Gang Mo; Yi Zhang; Jian-Hua Liang; Yu-Sha Yang; Yong Zhou; Zhao-Hua Li; Jian-Liang Zhang; Yin-Lu Ding; Peng Zhang; Jin-Qing Wang (Genes & Genomics, 2015)

Differential expression and regulation of Runx1 in mouse uterus during the peri-implantation period - Zhi-Kun Bai; Dang-Dang Li; Chuan-Hui Guo; Zhan-Qing Yang; Hang Cao; Bin Guo; Zhan-Peng Yue (Cell and Tissue Research, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Identification of Genes Involved in the Biosynthesis of Tripterygium wilfordii Hook.f. Secondary Metabolites by Suppression Subtractive Hybridization - Guo-peng Miao; Wei Li; Bin Zhang; Zhan-feng Zhang; Zhi-qing Ma; Jun-tao Feng; Xing Zhang; Chuan-shu Zhu (Plant Molecular Biology Reporter, 2015)

NCoR negatively regulates adipogenic differentiation of mesenchymal stem cells - Gao Hong-Wei; Liu Lan; Xing De-Guo; Liu Zhong-Hao; Ren Peng; Li Zhi-Qiang; Shan Guo-Qiang; Gong Ming-Zhi (In Vitro Cellular & Developmental Biology - Animal, 2015)

Large deformation failure analysis of the soil slope based on the material point method - Peng Huang; Shun-li Li; Hu Guo; Zhi-ming Hao (Computational Geosciences, 2015)

Cloning of a caffeoyl-coenzyme A O-methyltransferase from Camellia sinensis and analysis of its catalytic activity - Yue Zhang; Hai-peng Lv; Cheng-ying Ma; Li Guo; Jun-feng Tan; Qun-hua Peng; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Simultaneous quantification of 10 saponins in Chinese Shizhu Panax by UPLC-ESI-MS - Qi Jiang; Long-Shan Zhao; Zhi-Li Xiong; Xu-Ling Peng; Xing-Jie Guo (Natural Product Research, 2015)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Numerical analysis of adaptation-to-capacity length for fluvial sediment transport - Zhi-jing Li; Zhi-xian Cao; Gareth Pender; Peng Hu (Journal of Mountain Science, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

NDRG1 expression is related to the progression and prognosis of gastric cancer patients through modulating proliferation, invasion and cell cycle of gastric cancer cells - Xiaojing Chang; Xiaoyang Xu; Jinguo Ma; Xiaoying Xue; Zhenhua Li; Peng Deng; Shuanglong Zhang; Yu Zhi; Jing Chen; Dongqiu Dai (Molecular Biology Reports, 2014)

A field study of the relationship between sulfide-bound metals and bioaccumulation by Limnodrilus sp. in a heavily polluted river - Feng Li; Xiang-yun Zeng; Yun-jun Yu; Chang-hua Wu; Ge Mai; Wei-wei Song; Yan-mao Wen; Zhi-peng Duan; Jia-yu Yang (Environmental Monitoring and Assessment, 2014)

A Randomized and Controlled Multicenter Prospective Study of the Chinese Medicinal Compound Fufang Xuelian Burn Ointment for the Treatment of Superficial and Deep Second-Degree Burn Wounds - Jing Ouyang; Yong-chuan Chen; Gao-xing Luo; Hong Yan; Yi-zhi Peng; Yue-sheng Huang; Pei-yuan Xia; Qin Zhang; Zhen-jiang Liao; Guo-hui Li; Xiao-dong Yang; Yong-qing Cai (Cell Biochemistry and Biophysics, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Aroma changes of black tea prepared from methyl jasmonate treated tea plants - Jiang Shi; Li Wang; Cheng-ying Ma; Hai-peng Lv; Zong-mao Chen; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2014)

Construction and optimization of a Pseudomonas putida whole-cell bioreporter for detection of bioavailable copper - Peng-Song Li; Zhi-Wen Peng; Jie Su; Hu-Chun Tao (Biotechnology Letters, 2014)

Role of Unfolded Protein Response in Affecting Osteoblast Differentiation Induced by Fluoride - Xi-ning Li; Peng Lv; Zhi Sun; Guang-sheng Li; Hui Xu (Biological Trace Element Research, 2014)

Establishment and characterization of dairy cow growth hormone secreting anterior pituitary cell model - Jian-Fa Wang; Shou-Peng Fu; Su-Nan Li; Zhan-Qing Yang; Wen-Jing Xue; Zhi-Qiang Li; Wei Wang; Ju-Xiong Liu (In Vitro Cellular & Developmental Biology - Animal, 2014)

Comparative study of models for predicting permeability from nuclear magnetic resonance (NMR) logs in two Chinese tight sandstone reservoirs - Liang Xiao; Xiao-Peng Liu; Chang-Chun Zou; Xiao-Xin Hu; Zhi-Qiang Mao; Yu-Jiang Shi; Hao-Peng Guo; Gao-Ren Li (Acta Geophysica, 2014)

Association between the TP53 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Zhi-Bin Bu; Jie Feng; Ling Peng; Xin-Biao Liao; Xin-Li Zhu; Xiao-li Sun; Hao-Gang Yu; Dan-Fang Yan; Sen-Xiang Yan (Molecular Biology Reports, 2014)

Changes in some soil properties induced by re-conversion of cropland into grassland in the semiarid steppe zone of Inner Mongolia, China - Zhi-Hua Zhang; Xiao-Yan Li; Zhi-Yun Jiang; Hai-Ying Peng; Liu Li; Guo-Qin Zhao (Plant and Soil, 2013)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Multiple attenuation using λ-f domain high-resolution Radon transform - Zhi-Na Li; Zhen-Chun Li; Peng Wang; Qiang Xu (Applied Geophysics, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Bacillus oceani sp. nov., a new slightly halophilic bacterium, isolated from a deep sea sediment environment - Yu-Juan Liu; Li-Juan Long; Xiao-Fang Huang; Zhi-Qing You; Fa-Zuo Wang; Jie Li; Chang-Jin Kim; Xin-Peng Tian; Si Zhang (Antonie van Leeuwenhoek, 2013)

Expression and regulation of Runx3 in mouse uterus during the peri-implantation period - Zhi-Kun Bai; Bin Guo; Xue-Chao Tian; Dang-Dang Li; Shou-Tang Wang; Hang Cao; Qu-Yuan Wang; Zhan-Peng Yue (Journal of Molecular Histology, 2013)

Cytochrome P450 oxidoreductase genetic polymorphisms A503V and rs2868177 do not significantly affect warfarin stable dosage in Han-Chinese patients with mechanical heart valve replacement - Sheng-Lan Tan; Zhi Li; Wei Zhang; Guo-Bao Song; Li-Ming Liu; Juan Peng; Zhao-Qian Liu; Lan Fan; Xiang-Guang Meng; Lian-Sheng Wang; Yao Chen; Xin-Min Zhou; et al. (European Journal of Clinical Pharmacology, 2013)

Changes in carbon, nutrients and stoichiometric relations under different soil depths, plant tissues and ages in black locust plantations - Hong Li; Jing Li; Yalong He; Shaojun Li; Zongsuo Liang; Changhui Peng; Andrea Polle; Zhi-Bin Luo (Acta Physiologiae Plantarum, 2013)

Optimizing cadmium and mercury specificity of CadR-based E. coli biosensors by redesign of CadR - Hu-Chun Tao; Zhi-Wen Peng; Peng-Song Li; Tai-An Yu; Jie Su (Biotechnology Letters, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Targeted editing of goat genome with modular-assembly zinc finger nucleases based on activity prediction by computational molecular modeling - Kai Xiong; Shanshan Li; Hongxiao Zhang; Ye Cui; Debing Yu; Yan Li; Wenxing Sun; Yingying Fu; Yun Teng; Zhi Liu; Xiaolong Zhou; Peng Xiao; et al. (Molecular Biology Reports, 2013)

Paracoccus zhejiangensis sp. nov., isolated from activated sludge in wastewater-treatment system - Zhi-Guo Wu; Dao-Feng Zhang; Ya-Long Liu; Fang Wang; Xin Jiang; Chao Li; Shun-Peng Li; Qing Hong; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

A new phenylpropanoid from Peperomia tetraphylla - Yun-Zhi Li; Dai-Yin Peng; Min Dai; Cao-Mao Xiao; Hong-Bo Jiang; Jing Huang (Natural Product Research, 2013)

The Very Large G Protein Coupled Receptor (Vlgr1) in Hair Cells - Jin-Peng Sun; Rong Li; Hong-Ze Ren; An-Ting Xu; Xiao Yu; Zhi-Gang Xu (Journal of Molecular Neuroscience, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Bacillus abyssalis sp. nov., isolated from a sediment of the South China Sea - Zhi-Qing You; Jie Li; Sheng Qin; Xin-Peng Tian; Fa-Zuo Wang; Si Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Net fluxes of ammonium and nitrate in association with H+ fluxes in fine roots of Populus popularis - Jie Luo; Jingjing Qin; Fangfang He; Hong Li; Tongxian Liu; Andrea Polle; Changhui Peng; Zhi-Bin Luo (Planta, 2013)

Cadmium tolerance in six poplar species - Jiali He; Chaofeng Ma; Yonglu Ma; Hong Li; Jingquan Kang; Tongxian Liu; Andrea Polle; Changhui Peng; Zhi-Bin Luo (Environmental Science and Pollution Research, 2013)

Transforming growth factor-β1 induces matrix metalloproteinase-9 expression in rat vascular smooth muscle cells via ROS-dependent ERK–NF-κB pathways - Hao Zhang; Zhi-Wei Wang; Hong-Bing Wu; Zhi Li; Luo-Cheng Li; Xiao-Ping Hu; Zong-Li Ren; Bai-Jun Li; Zhi-Peng Hu (Molecular and Cellular Biochemistry, 2012)

Effects of recombinant hIL-2-Luffin P1 immunotoxin combining with arotinoid ethylester on the proliferation and apoptosis of Hut-78 cells - Shu-lei Liu; Wei He; Ru-peng Wang; Zhi Li; Ju Wu; Yun Zhao; Xiao-hong Hu (Molecular & Cellular Toxicology, 2012)

Phylogenetic analysis of the bovine parainfluenza virus type 3 from cattle herds revealing the existence of a genotype A strain in China - Yong-Jun Wen; Xin-Chuan Shi; Feng-Xue Wang; Wei Wang; Shu-Qin Zhang; Guo Li; Ni Song; Li-Zhi Chen; Shi-Peng Cheng; Hua Wu (Virus Genes, 2012)

Patterns of flower morphology and sexual systems in the subnival belt of the Hengduan Mountains, SW China - De-Li Peng; Zhi-Qiang Zhang; Bo Xu; Zhi-Min Li; Hang Sun (Alpine Botany, 2012)

Pseudomonas nitritireducens sp. nov., a nitrite reduction bacterium isolated from wheat soil - Ya-Nan Wang; Wei-Hong He; Hua He; Xun Du; Bin Jia; Zhi-Peng Zeng; Ming-Li An; Guo-Can Chen (Archives of Microbiology, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Passive stretch reduces calpain activity through nitric oxide pathway in unloaded soleus muscles - Peng-Tao Xu; Quan Li; Juan–Juan Sheng; Hui Chang; Zhen Song; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2012)

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

Micromonospora haikouensis sp. nov., isolated from mangrove soil - Qing-yi Xie; Zhi Qu; Hai-peng Lin; Lei Li; Kui Hong (Antonie van Leeuwenhoek, 2012)

Bufalin enhances the anti-proliferative effect of sorafenib on human hepatocellular carcinoma cells through downregulation of ERK - Yang Gao; Hua-Xing Li; Li-Tao Xu; Peng Wang; Li-Yan Xu; Lorenzo Cohen; Pei-Ying Yang; Ke Gu; Zhi-Qiang Meng (Molecular Biology Reports, 2012)

Effects of carboxymethyl-chitosan on wound healing in vivo and in vitro - Sikai Peng; Wanshun Liu; Baoqin Han; Jing Chang; Minyu Li; Xuan Zhi (Journal of Ocean University of China, 2011)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Tetanic contractions impair sarcomeric Z-disk of atrophic soleus muscle via calpain pathway - Xiao-Wu Ma; Quan Li; Peng-Tao Xu; Lin Zhang; Hui Li; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2011)

Expression, Characterization, and Site-Directed Mutation of a Multiple Herbicide-Resistant Acetohydroxyacid Synthase (rAHAS) from Pseudomonas sp. Lm10 - Zhi-Fei Lang; Jing-Jing Shen; Shu Cai; Jun Zhang; Jian He; Shun-Peng Li (Current Microbiology, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Movement patterns of Bar-headed Geese Anser indicus during breeding and post-breeding periods at Qinghai Lake, China - Peng Cui; Yuansheng Hou; Mingjie Tang; Haiting Zhang; Yuanchun Zhou; Zuohua Yin; Tianxian Li; Shan Guo; Zhi Xing; Yubang He; Diann J. Prosser; Scott H. Newman; et al. (Journal of Ornithology, 2011)

Differentially Expressed Outer Membrane Proteins of Vibrio alginolyticus in Response to Six Types of Antibiotics - Xiao-Peng Xiong; Chao Wang; Ming-Zhi Ye; Tian-Ci Yang; Xuan-Xian Peng; Hui Li (Marine Biotechnology, 2010)

Corpus Callosum: a Favorable Target for rSFV-Mediated Gene Transfer to Rat Brain with Broad and Efficient Expression - Zhao-Jian Li; Peng Sun; Hong-Di Zhang; Shi-Fang Li; Xia Liu; Ren-Zhi Wang (Journal of Molecular Neuroscience, 2010)

Genetic dissection of a chromosomal region conferring hybrid sterility using multi-donors from Oryza glaberrima - Jiawu Zhou; Peng Xu; Xianneng Deng; Jing Li; Fengyi Hu; Guangyun Ren; Zhi Zhang; Yahong Luan; Wei Deng; Zhigang Zhao; Ling Jiang; Jianmin Wan; et al. (Euphytica, 2010)

A Comprehensive Study of Deep Catalytic Oxidation of Benzene, Toluene, Ethyl Acetate, and their Mixtures over Pd/ZSM-5 Catalyst: Mutual Effects and Kinetics - Chi He; Peng Li; Jie Cheng; Zheng-Ping Hao; Zhi-Ping Xu (Water, Air, & Soil Pollution, 2010)

Influences of gas bubble and ice density on ice thickness measurement by GPR - Zhi-Jun Li; Qing Jia; Bao-Sen Zhang; Matti Leppäranta; Peng Lu; Wen-Feng Huang (Applied Geophysics, 2010)

Mycotoxin Ochratoxin A-induced cell death and changes in oxidative metabolism of Arabidopsis thaliana - Xiao-Li Peng; Wen-Tao Xu; Yan Wang; Kun-Lun Huang; Zhi-hong Liang; Wei-wei Zhao; Yun-Bo Luo (Plant Cell Reports, 2010)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

Reciprocal regulation between M3 muscarinic acetylcholine receptor and protein kinase C-ε in ventricular myocytes during myocardial ischemia in rats - Peng-zhou Hang; Jing Zhao; Yu-ping Wang; Li-hua Sun; Yong Zhang; Li-li Yang; Na Zhao; Zhi-dan Sun; Yu-ying Mao; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Differential expression of salt tolerance related genes in Brassica campestris L. ssp. chinensis (L.) Makino var. communis Tsen et Lee - Yang Qiu; Xi-xiang Li; Hai-ying Zhi; Di Shen; Peng Lu (Journal of Zhejiang University-SCIENCE B, 2009)

Adsorption of lead(II) from aqueous solution onto Hydrilla verticillata - Ling-zhi Huang; Guang-ming Zeng; Dan-lian Huang; Li-feng Li; Peng-mian Huang; Chang-bin Xia (Biodegradation, 2009)

Relationships between endothelial nitric oxide synthase gene polymorphisms and osteoporosis in postmenopausal women - Shun-zhi Liu; Hong Yan; Wei-kun Hou; Peng Xu; Juan Tian; Li-fang Tian; Bo-feng Zhu; Jie Ma; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2009)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Lake-Level Change and Water Balance Analysis at Lake Qinghai, West China during Recent Decades - Xiao-Yan Li; He-Ye Xu; Yong-Liang Sun; Deng-Shan Zhang; Zhi-Peng Yang (Water Resources Management, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Streptomyces gulbargensis sp. nov., isolated from soil in Karnataka, India - Syed G. Dastager; Wen-Jun Li; Dayanand Agasar; Mudgulkar B. Sulochana; Shu-Kun Tang; Xin-Peng Tian; Xiao-Yang Zhi (Antonie van Leeuwenhoek, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Silicon’s organic pool and biological cycle in moso bamboo community of Wuyishan Biosphere Reserve - Zhen-ji Li; Peng Lin; Jian-yuan He; Zhi-wei Yang; Yi-ming Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Isolation and Characterization of a Carbendazim-Degrading Rhodococcus sp. djl-6 - Xu Jing-Liang; Gu Xiang-Yang; Shen Biao; Wang Zhi-Chun; Wang Kun; Li Shun-Peng (Current Microbiology, 2006)

Exploring the diversity of myxobacteria in a soil niche by myxobacteria‐specific primers and probes - Zhi‐Hong Wu; De‐Ming Jiang; Peng Li; Yue‐Zhong Li (Environmental Microbiology, 2006)

Exploring the diversity of myxobacteria in a soil niche by myxobacteria‐specific primers and probes - Zhi‐Hong Wu; De‐Ming Jiang; Peng Li; Yue‐Zhong Li (Environmental Microbiology, 2005)
Summary The diversity of myxobacteria in a soil niche was explored using culture‐dependent and ‐independent methods. Conventional cultivation for bacteriolytic myxobacteria produced six types of myxobacteria, which were identified as two Myxococcus spp., two Corallococcus spp., a Cystobacter sp. and a Nannocysts sp. Hybridization analysis of the soil bacterial 16S rRNA gene library with myxobacteria‐specific probes revealed that myxobacteria accounted for less than 1% in the bacterial community. A Cystobacterineae 16S rRNA genes‐rich library was further established from the soil DNA by polymerase chain reaction amplification with a Cystobacterineae‐specific primer combined with a universal bacterial primer. Screening of the special library using Cystobacterineae‐ and Sorangineae‐specific probes produced approximately 45% and 3% positive signals respectively. Sixty‐four positive clones were randomly selected for sequencing. Except three repeats, the sequences were diverse ranging from 0.3% to 21.3%, and homologous with the known myxobacteria at 77.6–99.8%, including 57 in Cystobacterineae, one close to Nannocystis and three much more distant from the known myxobacteria. The sequences in the Cystobacterineae can further be divided into at least 12 groups, of which most were unreported. The results suggest that myxobacteria in nature are much more diverse than were ever known, even in one soil niche.

Spatial and temporal distribution of carbon isotopes in soil organic matter at the Dinghushan Biosphere Reserve, South China - Qingqiang Chen; Chengde Shen; Yanmin Sun; Shaolin Peng; Weixi Yi; Zhi’an Li; Mantao Jiang (Plant and Soil, 2005)

Surgical management of gastric stump cancer: a report of 37 cases - Li Chen; Hua Tian; Jian Chen; Zhi-gang He; Si-feng Tao; Gurung Lokesh; Shu-you Peng (Journal of Zhejiang University-SCIENCE B, 2005)

Developmental analyses reveal early arrests of the spore-bearing parts of reproductive organs in unisexual flowers of cucumber (Cucumis sativus L.) - Su-Lan Bai; Yi-Ben Peng; Ji-Xin Cui; Hai-Tao Gu; Li-Yun Xu; Yi-Qin Li; Zhi-Hong Xu; Shu-Nong Bai (Planta, 2004)

Nectar production and transportation in the nectaries of the female Cucumis sativus L. flower during anthesis - Yi-Ben Peng; Yi-Qin Li; Yu-Jin Hao; Zhi-Hong Xu; Shu-Nong Bai (Protoplasma, 2004)

Characterization of soybean genomic features by analysis of its expressed sequence tags - Ai-Guo Tian; Jun Wang; Peng Cui; Yu-Jun Han; Hao Xu; Li-Juan Cong; Xian-Gang Huang; Xiao-Ling Wang; Yong-Zhi Jiao; Bang-Jun Wang; Yong-Jun Wang; Jin-Song Zhang; et al. (Theoretical and Applied Genetics, 2004)

DNA damage in the early primordial anther is closely correlated with stamen arrest in the female flower of cucumber ( Cucumis sativus L.) - Yu-Jin Hao; Dong-Hui Wang; Yi-Ben Peng; Su-Lan Bai; Li-Yun Xu; Yi-Qin Li; Zhi-Hong Xu; Shu-Nong Bai (Planta, 2003)

Delayed cardioprotection induced by nitroglycerin is mediated by alpha-calcitonin gene-related peptide - Zhi-Hong Zhou; Jun Peng; Feng Ye; Nian-Sheng Li; Han-Wu Deng; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Sustainable use of land resource and its evaluation in county area - Chi-mei Liao; Lan Li; Zhi-qiang Yan; Ding-xin Peng (Chinese Geographical Science, 2002)

Litter decomposition and nitrogen mineralization of soils in subtropical plantation forests of southern China, with special attention to comparisons between legumes and non-legumes - Zhi-an Li; Shao-lin Peng; Debbie J. Rae; Guo-yi Zhou (Plant and Soil, 2001)

THE CULTURE OF FIBROBLASTS FROM DIAPHRAGM OF GIANT PANDA - Zhi-Ming Han; Da-Yuan Chen; Jin-Song Li; Qing-Yuan Sun; Peng-Yang Wang; Yang Huang; Jun Du (In Vitro Cellular & Developmental Biology - Animal, 2001)